Enclosure material for power storage device, method for manufacturing the same, and power storage device

CN122996546APending Publication Date: 2026-10-27MITSUBISHI CHEM CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580021818.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-25
Filing Date
2025-03-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0012]然而,本发明人等的研究表明,若想要使用包含专利文献1、专利文献2所记载的聚酯膜的层叠体通过热熔接来形成袋体,则会产生如下问题:层叠体的聚酯膜的耐热性低,因此会在热熔接后的聚酯膜的表面产生白化,从而所得到的袋体的表面外观降低,或者层叠体熔接于热熔接中使用的热封棒

Benefits of technology

[0091]根据本发明,能提供成型性和耐热性优异的蓄电器件用外装材料。此外,根据本发明,还能提供该蓄电器件用外装材料的制造方法以及利用了该蓄电器件用外装材料的蓄电器件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996546A_ABST
    Figure CN122996546A_ABST
Patent Text Reader

Abstract

The present application provides an exterior material for an electrical storage device, which is excellent in moldability and heat resistance. An exterior material for an electrical storage device, which is composed of a laminate provided with a base material layer, a barrier layer, and a heat-fusible resin layer in this order, the base material layer being a polyester film containing polyethylene terephthalate and polybutylene terephthalate at a mass ratio of 65 / 35 to 90 / 10, the polyester film having a tensile elongation at break in the width direction of 90% or more and 155% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to casing materials for energy storage devices, methods for manufacturing the same, and energy storage devices. More specifically, it relates to casing materials for energy storage devices with excellent formability and heat resistance, methods for manufacturing the same, and energy storage devices. Background Technology

[0002] In energy storage devices, packaging materials (outer packaging materials) are used to seal electrodes, electrolytes, and other components. Historically, metal outer packaging materials have been the most common type of outer packaging material.

[0003] On the other hand, in recent years, with the increasing performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc., there are demands for lithium-ion batteries to have various shapes, as well as to be thinner and lighter. However, the metal casing materials that have been mostly used in the past have problems such as difficulty in keeping up with the diversity of shapes and the limitations of lightweighting.

[0004] Therefore, in recent years, bags (bags) made of laminated bodies consisting of plastic films layered on metal foils such as aluminum foil have been increasingly used as outer packaging materials that are easy to process into various shapes and can achieve thinness and lightweight. In such outer packaging materials, recesses are usually formed by cold forming the laminate, and energy storage devices such as electrodes and electrolytes are placed in the space formed by the recesses. The laminates are then thermally fused together, thereby obtaining lithium-ion batteries and the like, which contain energy storage devices inside the outer packaging material.

[0005] Polyamide is widely used as the substrate for this laminate, considering its excellent formability. In addition to formability, such outer materials sometimes require moisture resistance, sealing, puncture resistance, insulation, heat resistance, cold resistance, and chemical resistance. Therefore, the structure formed by laminates consisting of polyester film, polyamide film, metal foil, and sealing film stacked sequentially from the outside has also been studied.

[0006] In addition, in recent years, in order to efficiently house lithium-ion batteries along with printed circuit boards and other components within electronic devices that require miniaturization and thinning, it has been studied to make the corners of the pouches into sharp shapes. Furthermore, from the viewpoint of further improving the capacity and energy density of batteries per unit volume by increasing the content of each pouch (the volume of the containment portion), the development of films with excellent formability capable of forming deeper recesses in cold forming processes such as deep drawing has received more attention in recent years. For example, polyester films with polybutylene terephthalate as the main component have been disclosed (Patent Document 1, Patent Document 2).

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 2012-077292

[0010] Patent Document 2: International Publication No. 2014 / 017457 Summary of the Invention

[0011] The problem that the invention aims to solve

[0012] However, the present inventors' research shows that if a bag body is formed by heat-sealing a laminate containing the polyester film described in Patent Documents 1 and 2, the following problems arise: the polyester film of the laminate has low heat resistance, resulting in whitening on the surface of the polyester film after heat-sealing, thus reducing the surface appearance of the resulting bag body; or the laminate is welded to the heat-sealing bar used in heat-sealing. Furthermore, the present inventors' research shows that if the content of polybutylene terephthalate is reduced to improve heat resistance, even when using polyamide laminates with excellent deep-drawing properties, problems arise such as the indentation breaking if a deep indentation is to be formed.

[0013] Solution for solving the problem

[0014] In view of the above, the inventors have conducted repeated and in-depth research and found that in the outer casing material for a storage device, which is composed of at least a substrate layer, a barrier layer and a heat-welding resin layer in sequence, the substrate layer contains polyethylene terephthalate and polybutylene terephthalate in a specific ratio, and the tensile elongation at break in the width direction is controlled within a specific range. This suppresses local stress concentration during molding and promotes stress uniformity, thus achieving excellent formability and excellent heat resistance that can withstand heat fusion.

[0015] That is, the present invention provides the following content. [1]

[0017] An outer casing material for an energy storage device is provided, comprising at least a substrate layer, a barrier layer, and a heat-melting resin layer in sequence. The substrate layer is a polyester film containing polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 65 / 35 to 90 / 10, and the tensile elongation at break in the width direction of the polyester film is 90% or more and 155% or less. [2]

[0019] According to the outer casing material for the energy storage device described in [1], a polyamide layer is provided between the substrate layer and the barrier layer. [3]

[0021] According to the external material for energy storage devices described in [1] or [2], the tensile yield stress of the polyester film in the long dimension direction is 80 MPa or more and 105 MPa or less. [4]

[0023] The outer casing material for an energy storage device according to any one of [1] to [3], wherein the tensile yield stress in the width direction of the polyester film is 65 MPa or more and 110 MPa or less. [5]

[0025] The outer casing material for an energy storage device according to any one of [1] to [4], wherein the elongation at break of the polyester film in the long dimension is 110% or more and 190% or less. [6]

[0027] The outer casing material for an energy storage device according to any one of [1] to [5], wherein the tensile breaking stress in the longitudinal direction of the polyester film is 160 MPa or more and 260 MPa or less, and the tensile breaking stress in the width direction of the polyester film is 190 MPa or more and 290 MPa or less. [7]

[0029] The outer casing material for an energy storage device according to any one of [1] to [6], wherein the tensile elongation at break in the width direction of the polyester film is less than or equal to the tensile elongation at break in the length direction of the polyester film. [8]

[0031] The outer casing material for an energy storage device according to any one of [1] to [7], wherein the tensile breaking stress in the width direction of the polyester film is greater than or equal to the tensile breaking stress in the length direction of the polyester film. [9]

[0033] The outer casing material for an energy storage device according to any one of [1] to [8], wherein the slope of the curve corresponding to the yield point to the fracture point in the stress-strain curve of the polyester film is 0.60 MPa / % or more and 1.20 MPa / % or less in the long dimension direction, and 1.00 MPa / % or more and 1.80 MPa / % or less in the width direction.

[10]

[0035] According to the external material for the energy storage device described in [9], the absolute value of the difference between the slope of the curve in the long dimension direction and the slope of the curve in the width direction is less than 1.10 MPa / %.

[11]

[0037] The outer casing material for an energy storage device according to any one of [1] to

[10] , wherein the melting point of the polyester film during the first temperature scan is above 230°C.

[12]

[0039] The outer casing material for an energy storage device according to any one of [1] to

[11] , wherein an adhesive layer is provided between the substrate layer and the barrier layer.

[13]

[0041] The outer casing material for an energy storage device according to any one of [1] to

[12] , wherein a polyamide layer composed of a stretch film is provided between the substrate layer and the barrier layer.

[14]

[0043] The outer casing material for an energy storage device according to any one of [1] to

[13] , wherein the barrier layer comprises aluminum.

[15]

[0045] The outer casing material for an energy storage device according to any one of [1] to

[14] , wherein the polyester film is composed of two or more laminates.

[16]

[0047] The outer casing material for an energy storage device according to any one of [1] to

[15] , wherein the polyester film comprises a surface layer, an intermediate layer and a surface layer in sequence.

[17]

[0049] The outer casing material for an energy storage device according to any one of [1] to

[16] , wherein the polyester film comprises a surface layer, an intermediate layer and a surface layer in sequence, and the thickness of the intermediate layer is greater than the thickness of the surface layer.

[18]

[0051] The outer casing material for an energy storage device according to any one of [1] to

[17] , wherein the polyester film comprises a surface layer, an intermediate layer and a surface layer in sequence, and the thickness ratio of each layer (thickness of surface layer: thickness of intermediate layer: thickness of surface layer) is 1 to 1.6: 8 to 12: 1 to 1.6.

[19]

[0053] The outer casing material for an energy storage device according to any one of [1] to

[18] , wherein the polyester film is composed of two or more laminates, and the material composition forming one surface layer is different from the material composition forming at least one of the other layers.

[20]

[0055] The outer casing material for an energy storage device according to any one of [1] to

[19] , wherein the polyester film sequentially comprises a surface layer, an intermediate layer and a surface layer, and the material composition forming the surface layer is different from the material composition forming the intermediate layer. [twenty one]

[0057] The outer casing material for an energy storage device according to any one of [1] to

[20] , wherein the polyester film is composed of two or more laminates, wherein the content of polyethylene terephthalate in one surface layer is greater than the content of polyethylene terephthalate in at least one of the other layers. [twenty two]

[0059] The outer casing material for an energy storage device according to any one of [1] to

[21] , wherein the polyester film is composed of two or more laminates, wherein the content of polyethylene terephthalate in one surface layer is greater than the content of polyethylene terephthalate in at least one of the other layers, and the surface layer is present on the outermost side of the laminate. [twenty three]

[0061] The outer casing material for an energy storage device according to any one of [1] to

[22] , wherein the polyester film comprises a surface layer, an intermediate layer and a surface layer in sequence, wherein the content of polyethylene terephthalate in the surface layer is greater than the content of polyethylene terephthalate in the intermediate layer. [twenty four]

[0063] The outer casing material for an energy storage device according to any one of [1] to

[23] , wherein the polyester film is composed of two or more laminates, and one surface layer contains polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 100 / 0 to 90 / 10.

[25]

[0065] The outer casing material for an energy storage device according to any one of [1] to

[24] , wherein the polyester film is composed of two or more layers of laminate, and one surface layer contains polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 100 / 0 to 90 / 10, the surface layer being present on the outermost side of the laminate.

[26]

[0067] The outer casing material for an energy storage device according to any one of [1] to

[25] , wherein the polyester film comprises a surface layer, an intermediate layer and a surface layer in sequence, wherein the surface layer contains polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 100 / 0 to 90 / 10.

[27]

[0069] The outer casing material for the energy storage device according to any one of [1] to

[26] , wherein the melting peak of the polyester film at the time of heating is one of at least one of the first heating scan and the second heating scan obtained based on differential scanning calorimetry.

[28]

[0071] The outer casing material for an energy storage device according to any one of [1] to

[27] , wherein at least one surface of the polyester film has a coating.

[29]

[0073] The outer casing material for an energy storage device according to any one of [1] to

[28] , wherein at least one surface of the polyester film has a coating, the coating containing a long-chain alkyl compound and a melamine compound in a mass ratio of 95 / 5 to 5 / 95.

[30]

[0075] The outer casing material for an energy storage device according to any one of [1] to

[29] , wherein the intrinsic viscosity of the polyethylene terephthalate contained in the polyester film is 0.50 dL / g or higher.

[31]

[0077] The outer casing material for the storage device according to any one of [1] to

[30] , wherein the intrinsic viscosity of the polybutylene terephthalate contained in the polyester film is 0.70 dL / g or higher.

[32]

[0079] The outer casing material for an energy storage device according to any one of [1] to

[31] , wherein the polyester film is a biaxially stretched film and the product of the stretch ratio in the width direction and the stretch ratio in the length direction of the polyester film exceeds 15.5.

[33]

[0081] The outer casing material for the storage device according to any one of [1] to

[32] , wherein the polyester film is a biaxially stretched film, and the difference between the stretch ratio in the width direction and the stretch ratio in the length direction of the polyester film is more than 0.3 times.

[34]

[0083] The outer casing material for an energy storage device according to any one of [1] to

[33] , wherein the polyester film is a biaxially stretched film, and the ratio of the stretch ratio in the width direction to the stretch ratio in the length direction of the polyester film (stretch ratio in the width direction / stretch ratio in the length direction) is 1.2 or more and 1.7 or less.

[35]

[0085] An energy storage device comprising an energy storage device element having at least a positive electrode, a negative electrode and an electrolyte, contained in a package made of an outer packaging material for an energy storage device as described in any one of [1] to

[34] .

[36]

[0087] A method for manufacturing an outer casing material for an energy storage device includes a step of sequentially stacking at least a substrate layer, a barrier layer, and a heat-melting resin layer to obtain a laminate. The substrate layer uses a polyester film containing polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 65 / 35 to 90 / 10. The polyester film has a tensile elongation at break in the width direction of 90% or more and 155% or less.

[37]

[0089] According to the manufacturing method of the outer casing material for the energy storage device described in

[36] , the process of obtaining the laminate is a process of obtaining a laminate having at least a substrate layer, a polyamide layer, a barrier layer and a heat-melting resin layer in sequence, wherein the tensile yield stress of the polyester film in the long dimension direction is 80 MPa or more and 105 MPa or less, the tensile yield stress of the polyester film in the width direction is 65 MPa or more and 110 MPa or less, and the tensile elongation at break of the polyester film in the long dimension direction is 110% or more and 190% or less.

[0090] Invention Effects

[0091] According to the present invention, an outer casing material for energy storage devices with excellent formability and heat resistance can be provided. Furthermore, according to the present invention, a method for manufacturing the outer casing material for energy storage devices and an energy storage device utilizing the outer casing material can also be provided. Attached Figure Description

[0092] Figure 1 This is a schematic cross-sectional view showing an example of the cross-sectional structure of the outer casing material for the energy storage device of the present invention.

[0093] Figure 2 This is a schematic top view of the outer casing material for the energy storage device of the present invention.

[0094] Figure 3 yes Figure 2 A schematic cross-sectional view at line A-A'. Detailed Implementation

[0095] The present invention will now be described in more detail based on embodiments thereof, but the present invention is not limited to these embodiments.

[0096] It should be noted that in this specification, when expressed as "X~Y" (where X and Y are arbitrary numbers), unless otherwise specified, it includes the endpoints and their range. That is, it means that it includes X, the range between X and Y, and Y.

[0097] Furthermore, in this specification, "X and / or Y (X and Y can be any configuration)" means at least one of X and Y, and specifically refers to X only, Y only, or X and Y.

[0098] Furthermore, in this specification, the term "film" also includes "sheet" when referred to as "membrane," and the term "sheet" also includes "film."

[0099] Furthermore, in this specification, "main component" refers to the component that has a significant impact on the properties of the material. This component is the component with the highest content in the whole material, and its content is usually 60% or more by mass of the whole material, preferably 65% ​​or more by mass, more preferably 70% or more by mass, and may also be 80 to 100% by mass or 90 to 100% by mass.

[0100] <<This exterior material>>

[0101] The outer casing material for a storage device according to one embodiment of the present invention (hereinafter, sometimes referred to as "this outer casing material") is not limited to the following, for example, such as Figure 1 As shown, the battery is composed of a laminate consisting of a substrate layer 1, a first adhesive layer 2, a polyamide layer 3, a second adhesive layer 4, a barrier layer 5, and a heat-melting resin layer 6, in sequence. The substrate layer 1 is the outermost layer, and the heat-melting resin layer 6 is the innermost layer. That is, during battery assembly, the heat-melting resin layers 6 located around the periphery of the battery element are heat-melted together to seal the battery element, thereby sealing the battery element.

[0102] There are no particular limitations on the thickness (total thickness) of the laminate constituting the outer casing material. However, from the viewpoint of cost reduction and increased energy density, it is preferably about 300 μm or less, and more preferably about 250 μm or less, about 220 μm or less, about 180 μm or less, about 155 μm or less, or about 120 μm or less. Furthermore, from the viewpoint of maintaining the function of the outer casing material in protecting the energy storage device elements, the thickness (total thickness) of the laminate constituting the outer casing material is preferably about 35 μm or more, about 45 μm or more, or about 60 μm or more. Furthermore, the preferred range of thickness (total thickness) of the laminate constituting the outer casing material is, for example, approximately 35–300 μm, approximately 35–250 μm, approximately 35–220 μm, approximately 35–180 μm, approximately 35–155 μm, approximately 35–120 μm, approximately 45–300 μm, approximately 45–250 μm, approximately 45–220 μm, approximately 45–180 μm, approximately 45–155 μm, approximately 45–120 μm, approximately 60–300 μm, approximately 60–250 μm, approximately 60–220 μm, approximately 60–180 μm, approximately 60–155 μm, approximately 60–120 μm, with a particularly preferred thickness of approximately 60–250 μm.

[0103] In this exterior material, the total thickness of the substrate layer 1, the first adhesive layer 2, the polyamide layer 3, the second adhesive layer 4, the barrier layer 5, the heat-melting resin layer 6, and the third adhesive layer, as required, is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more, relative to the thickness (total thickness) of the laminate constituting this exterior material.

[0104] It should be noted that in this outer casing material, regarding the barrier layer 5 described later, its MD (Machine Direction) and TD (Transverse Direction) during the manufacturing process can usually be determined. When the barrier layer 5 is made of aluminum alloy foil, linear stripes known as rolling marks are formed on the surface of the foil along its rolling direction (RD). The rolling marks extend along the rolling direction, so the rolling direction of the foil can be determined by observing its surface. Furthermore, during the manufacturing process of the laminate, the MD of the laminate is usually aligned with the RD of the foil; therefore, by observing the surface of the foil in the laminate and determining the rolling direction (RD), the MD of the laminate can be determined. Additionally, the TD of the laminate is perpendicular to its MD, so the TD of the laminate can also be determined.

[0105] Furthermore, if the material density (MD) of the outer casing material cannot be determined by the rolling marks of the aluminum alloy foil, it can be determined by the following method. One method for confirming the MD of the outer casing material is to observe the cross-section of the thermosetting resin layer of the outer casing material using an electron microscope to confirm the island structure. In this method, the direction parallel to the cross-section in which the average diameter of the island shape in the direction perpendicular to the thickness direction of the thermosetting resin layer is maximized is determined as the MD. Specifically, the island structure is confirmed by observing electron microscope images of each of the following 10 cross-sections: a cross-section along the long dimension of the thermosetting resin layer, and a cross-section extending from a direction parallel to the long dimension, changing the angle every 10 degrees until it reaches a direction perpendicular to the long dimension. Then, the shape of each island is observed in each cross-section. Regarding the shape of each island, the straight-line distance connecting the leftmost end and the rightmost end in the direction perpendicular to the thickness direction of the thermosetting resin layer is defined as the diameter y. In each cross-section, the average value of the first 20 diameters y is calculated in descending order of the island's shape. The direction parallel to the cross-section with the largest average diameter y of the island's shape is designated as MD.

[0106] Each layer of the outer casing material for energy storage devices

[0107] <Substrate Layer 1>

[0108] The substrate layer 1 is a layer designed to provide the heat resistance, formability, and dimensional stability of the substrate used as the outer material, and is composed of a specific polyester film (hereinafter sometimes referred to as "this polyester film").

[0109] From the viewpoint of balancing the formability and heat resistance of this outer casing material, the mass ratio (PET / PBT) of polyethylene terephthalate (PET) to polybutylene terephthalate (PBT) in this polyester film is 65 / 35 to 90 / 10. In the mass ratio of PET to PBT contained in this polyester film, the mass ratio of PET is preferably 67 or more, more preferably 69 or more, even more preferably 70 or more, and particularly preferably 71 or more. Furthermore, it is preferably 88 or less, more preferably 87 or less, even more preferably 86 or less, particularly preferably 85 or less, even more preferably 83 or less, even more preferably 82 or less, and even more preferably 80 or less. In the polyester film, the mass ratio of polyethylene terephthalate (PET) to polybutylene terephthalate (PBT) is preferably 12 or more, more preferably 13 or more, even more preferably 14 or more, even more preferably 15 or more, particularly preferably 17 or more, even more preferably 18 or more, and even more preferably 20 or more. Furthermore, it is preferably 33 or less, more preferably 31 or less, even more preferably 30 or less, and particularly preferably 29 or less.Furthermore, the mass ratio in this polyester film is approximately 65 / 35 to 90 / 10, for example, approximately 67 / 33 to 90 / 10, approximately 69 / 31 to 90 / 10, approximately 70 / 30 to 90 / 10, approximately 71 / 29 to 90 / 10, approximately 65 / 35 to 88 / 12, for example, approximately 67 / 33 to 88 / 12, approximately 69 / 31 to 88 / 12, approximately 70 / 30 to 88 / 12. Approximately 71 / 29 to 88 / 12, 65 / 35 to 87 / 13, for example, 67 / 33 to 87 / 13, 69 / 31 to 87 / 13, 70 / 30 to 87 / 13, 71 / 29 to 87 / 13, 65 / 35 to 86 / 14, 67 / 33 to 86 / 14, 69 / 31 to 86 / 14, 70 / 30 to 86 / 14, 71 / Approximately 29-86 / 14, 65 / 35-85 / 15, 67 / 33-85 / 15, 69 / 31-85 / 15, 70 / 30-85 / 15, 71 / 29-85 / 15, 65 / 35-83 / 17, 67 / 33-83 / 17, 69 / 31-83 / 17, 70 / 30-83 / 17, 71 / 29-83 Around 17, 65 / 35 to 82 / 18, 67 / 33 to 82 / 18, 69 / 31 to 82 / 18, 70 / 30 to 82 / 18, 71 / 29 to 82 / 18, 65 / 35 to 80 / 20, 67 / 33 to 80 / 20, 69 / 31 to 80 / 20, 70 / 30 to 80 / 20, 71 / 29 to 80 / 20.

[0110] If the mass ratio (PET / PBT) is outside the stated range, it is difficult to balance moldability and heat resistance.

[0111] [Tension Elongation at Break]

[0112] From the viewpoint of balancing the formability and heat resistance of the outer casing material, the tensile elongation at break in the width direction (TD) of this polyester film is 90% or more and 155% or less. That is, the tensile elongation at break in the width direction (TD) is 90% or more, preferably 95% or more, more preferably 100% or more, even more preferably 105% or more, and particularly preferably 110% or more. Furthermore, it is 155% or less, preferably 153% or less, more preferably 150% or less, even more preferably 148% or less, even more preferably 145% or less, particularly preferably 140% or less, and even more particularly preferably 130% or less. Furthermore, the range of tensile elongation at break in the width direction (TD) of this polyester film is 90–155%, for example, approximately 95–155%, approximately 100–155%, approximately 105–155%, approximately 110–155%, approximately 90–153%, approximately 95–153%, approximately 100–153%, approximately 105–153%, approximately 110–153%, approximately 90–150%, approximately 95–150%, approximately 100–150%, approximately 105–150%, approximately 110–150%, and approximately 90–148%. Approximately 95-148%, 100-148%, 105-148%, 110-148%, 90-145%, 95-145%, 100-145%, 105-145%, 110-145%, 90-140%, 95-140%, 100-140%, 105-140%, 110-140%, 90-130%, 95-130%, 100-130%, 105-130%, 110-130%.

[0113] If the tensile elongation at break in the width direction (TD) of this polyester film is outside the range described, it is difficult to achieve both formability and heat resistance.

[0114] Furthermore, from the viewpoint of balancing the formability and heat resistance of the outer casing material, the elongation at break in the longitudinal dimension (MD) of the polyester film is preferably 110% or more and 190% or less. That is, the elongation at break in the longitudinal dimension (MD) is, for example, 110% or more, preferably 120% or more, more preferably 128% or more, even more preferably 135% or more, and particularly preferably 145% or more. Moreover, it is, for example, 190% or less, preferably 188% or less, more preferably 182% or less, and even more preferably 180% or less. Furthermore, the range of tensile elongation at break in the longitudinal dimension (MD) of this polyester film is, for example, approximately 110–190%, 120–190%, 128–190%, 135–190%, 145–190%, 110–188%, 120–188%, 128–188%, 135–188%, 145–188%, 110–182%, 120–182%, 128–182%, 135–182%, 145–182%, 110–180%, 120–180%, 128–180%, 135–180%, and 145–180%.

[0115] From the viewpoint of balancing the formability and heat resistance of the outer casing material, the elongation at break in the width direction (TD) of the polyester film is preferably less than or equal to the elongation at break in the length direction (MD) of the polyester film (elongation at break in the width direction (TD) ≤ elongation at break in the length direction (MD)), and more preferably less than the elongation at break in the length direction of the polyester film (elongation at break in the width direction (TD) < elongation at break in the length direction (MD)). Furthermore, for example, the difference between the elongation at break in the width direction (TD) and the elongation at break in the length direction (MD) of the polyester film (elongation at break in the length direction (MD) [%] - elongation at break in the width direction (TD) [%]) is, for example, about 5 to 60%, preferably about 8 to 55%, and more preferably about 10 to 52%. The difference between the elongation at break in the width direction (TD) and the elongation at break in the length direction (MD) of this polyester film (elongation at break in the length direction (MD) [%] - elongation at break in the width direction (TD) [%]) can be less than 50%, less than 46%, less than 42%, less than 36%, less than 32%, less than 28%, or less than 24%.

[0116] [Tension yield stress]

[0117] From the viewpoint of balancing the formability and heat resistance of the outer casing material, the tensile yield stress in the longitudinal dimension (MD) of the polyester film is preferably 80 MPa or more and 105 MPa or less. That is, the tensile yield stress in the longitudinal dimension (MD) is, for example, 80 MPa or more, preferably 81 MPa or more, more preferably 82 MPa or more, and even more preferably 83 MPa or more. Furthermore, it is, for example, 105 MPa or less, preferably 103 MPa or less, more preferably 102 MPa or less, and even more preferably 100 MPa or less. Furthermore, the range of tensile yield stress in the longitudinal dimension (MD) of this polyester film is, for example, approximately 80–105 MPa, approximately 81–105 MPa, approximately 82–105 MPa, approximately 83–105 MPa, approximately 80–103 MPa, approximately 81–103 MPa, approximately 82–103 MPa, approximately 83–103 MPa, approximately 80–102 MPa, approximately 81–102 MPa, approximately 82–102 MPa, approximately 83–102 MPa, approximately 80–100 MPa, approximately 81–100 MPa, approximately 82–100 MPa, and approximately 83–100 MPa.

[0118] Furthermore, considering both the formability and heat resistance of the outer casing material, the tensile yield stress in the width direction (TD) of the polyester film is preferably 65 MPa or more and 110 MPa or less. That is, the tensile yield stress in the width direction (TD) is preferably 65 MPa or more, 68 MPa or more, more preferably 72 MPa or more, and even more preferably 75 MPa or more. Furthermore, it is preferably 110 MPa or less, 109 MPa or less, more preferably 107 MPa or less, and even more preferably 105 MPa or less. Furthermore, the range of tensile yield stress in the width direction (TD) of this polyester film is, for example, approximately 65–110 MPa, approximately 68–110 MPa, approximately 72–110 MPa, approximately 75–110 MPa, approximately 65–109 MPa, approximately 68–109 MPa, approximately 72–109 MPa, approximately 75–109 MPa, approximately 65–107 MPa, approximately 68–107 MPa, approximately 72–107 MPa, approximately 75–107 MPa, approximately 65–105 MPa, approximately 68–105 MPa, approximately 72–105 MPa, and approximately 75–105 MPa.

[0119] [Tensile fracture stress]

[0120] From the viewpoint of balancing the formability and heat resistance of the outer casing material, the tensile breaking stress in the longitudinal dimension (MD) of the polyester film is preferably 160 MPa or more and 260 MPa or less. That is, the tensile breaking stress in the longitudinal dimension (MD) is, for example, 160 MPa or more, preferably 170 MPa or more, more preferably 175 MPa or more, even more preferably 180 MPa or more, particularly preferably 190 MPa or more, even more preferably 195 MPa or more, and even more preferably 200 MPa or more. Furthermore, it is, for example, 260 MPa or less, preferably 255 MPa or less, more preferably 250 MPa or less, even more preferably 245 MPa or less, particularly preferably 240 MPa or less, even more preferably 235 MPa or less, even more preferably 230 MPa or less, and even more preferably 227 MPa or less. Furthermore, the range of tensile breaking stress in the longitudinal dimension (MD) of this polyester film is, for example, about 160 to 260 MPa, preferably about 170 to 255 MPa, more preferably about 175 to 250 MPa, even more preferably about 180 to 245 MPa, particularly preferably about 190 to 240 MPa, even more particularly preferably about 195 to 245 MPa, and even more particularly preferably about 200 to 240 MPa.

[0121] Furthermore, considering both the formability and heat resistance of the outer casing material, the tensile breaking stress in the width direction (TD) of the polyester film is preferably 190 MPa or more and 290 MPa or less. That is, the tensile breaking stress in the width direction (TD) is, for example, 190 MPa or more, preferably 200 MPa or more, more preferably 220 MPa or more, even more preferably 230 MPa or more, and particularly preferably 240 MPa or more. Furthermore, it is, for example, 290 MPa or less, preferably 285 MPa or less, more preferably 282 MPa or less, and even more preferably 280 MPa or less. Moreover, regarding the range of the tensile breaking stress in the width direction (TD) of the polyester film, it is, for example, about 190 to 290 MPa, preferably about 200 to 290 MPa, more preferably about 220 to 285 MPa, even more preferably about 230 to 280 MPa, and particularly preferably about 240 to 282 MPa.

[0122] From the viewpoint of balancing the formability and heat resistance of the outer casing material, the tensile breaking stress in the width direction (TD) of the polyester film is preferably greater than or equal to the tensile breaking stress in the length direction (MD) of the polyester film (tensile breaking stress in the width direction (TD) ≥ tensile breaking stress in the length direction (MD)), and more preferably greater than the tensile breaking stress in the length direction (MD) of the polyester film (tensile breaking stress in the width direction (TD) > tensile breaking stress in the length direction (MD)). Furthermore, for example, the difference between the tensile breaking stress in the width direction (TD) and the tensile breaking stress in the length direction (MD) of the polyester film (tensile breaking stress in the width direction (TD) [MPa] - tensile breaking stress in the length direction (MD) [MPa]) is, for example, 5 to 80 MPa, preferably about 8 to 75 MPa, and more preferably about 10 to 70 MPa. The difference between the tensile breaking stress in the width direction (TD) and the tensile breaking stress in the length direction (MD) of this polyester film (tensile breaking stress in the width direction (TD) [MPa] - tensile breaking stress in the length direction (MD) [MPa]) can be less than 65MPa, less than 60MPa, less than 55MPa, less than 50MPa, less than 45MPa, less than 40MPa, or less than 35MPa.

[0123] The tensile yield stress, tensile elongation at break, and tensile stress at break can be determined according to JIS K 7161-1 (2014). Specifically, a sample sheet can be collected from a polyester film, and the tensile yield stress, tensile elongation at break, and tensile stress at break can be determined using a tensile testing machine in both the longitudinal (MD) and transverse (TD) directions, according to JIS K 7161-1 (2014). The test conditions are 23°C, 50%RH atmosphere, 50 mm chuck spacing for the sample sheet, and tensile speed of 200 mm / min.

[0124] It should be noted that in this specification, "elongation at break" refers to either "tensile failure strain" or "nominal tensile failure strain" (refer to JIS K 7161-1 (2014)) which are determined based on the characteristics of the stress / strain curve of the membrane being measured.

[0125] [The slope of the curve between the yield point and the fracture point in the stress-strain curve]

[0126] From the viewpoint of balancing the formability and heat resistance of the outer casing material, the slope of the curve along the longitudinal dimension (MD) of the polyester film is preferably 0.60 MPa / % or more and 1.20 MPa / % or less. That is, from the viewpoint of balancing the formability and heat resistance of the outer casing material, the slope of the curve along the longitudinal dimension (MD) is, for example, 0.60 MPa / % or more, preferably 0.65 MPa / % or more, and more preferably 0.68 MPa / % or more. Furthermore, it is, for example, 1.20 MPa / % or less, preferably 1.10 MPa / % or less, more preferably 1.05 MPa / % or less, even more preferably 1.00 MPa / % or less, particularly preferably 0.98 MPa / % or less, and even more particularly preferably 0.97 MPa / % or less. Furthermore, the slope range of the curve in the longitudinal dimension (MD) direction of this polyester film is, for example, about 0.60 to 1.20 MPa / %, preferably about 0.60 to 1.10 MPa / %, more preferably about 0.65 to 1.05 MPa / %, even more preferably about 0.65 to 1.00 MPa / %, particularly preferably about 0.68 to 0.98 MPa / %, and even more particularly preferably about 0.68 to 0.97 MPa / %.

[0127] Furthermore, from the viewpoint of balancing the formability and heat resistance of the outer casing material, the slope of the curve in the width direction (TD) of the polyester film is preferably 1.00 MPa / % or more and 1.80 MPa / % or less. That is, the slope of the curve in the width direction (TD) is, for example, 1.00 MPa / % or more, preferably 1.05 MPa / % or more, more preferably 1.10 MPa / % or more, even more preferably 1.15 MPa / % or more, particularly preferably 1.20 MPa / % or more, even more preferably 1.30 MPa / % or more, even more preferably 1.35 MPa / % or more, and even more preferably 1.40 MPa / % or more. Furthermore, for example, it is 1.80 MPa / % or less, preferably 1.75 MPa / % or less, more preferably 1.70 MPa / % or less, even more preferably 1.65 MPa / % or less, and can be 1.60 MPa / % or less, or 1.55 MPa / % or less, or 1.50 MPa / % or less, or 1.45 MPa / % or less. Furthermore, the slope range of the curve in the width direction (TD) of this polyester film is, for example, about 1.00 to 1.80 MPa / %, preferably about 1.05 to 1.75 MPa / %, more preferably about 1.10 to 1.70 MPa / %, even more preferably about 1.15 to 1.65 MPa / %, particularly preferably about 1.20 to 1.60 MPa / %, even more preferably about 1.30 to 1.55 MPa / %, even more preferably about 1.35 to 1.50 MPa / %, and even more preferably about 1.40 to 1.45 MPa / %.

[0128] [The absolute value of the difference between the slopes of the stress-strain curves along the longitudinal dimension (MD) and the transverse dimension (TD)]

[0129] In this polyester film, from the viewpoint of highly balancing the formability and heat resistance of the outer casing material, the absolute value of the difference between the slope (MPa / %) of the curve corresponding to the yield point to the fracture point in the stress-strain curve along the longitudinal dimension (MD) and the slope (MPa / %) of the curve corresponding to the yield point to the fracture point in the stress-strain curve along the width direction (TD) is, for example, 1.10 MPa / % or less, preferably 1.05 MPa / % or less, more preferably 1.00 MPa / % or less, even more preferably 0.95 MPa / % or less, and particularly preferably 0.90 MPa / % or less. Furthermore, it is, for example, 0.20 MPa / % or more, preferably 0.25 MPa / % or more, more preferably 0.30 MPa / % or more, even more preferably 0.35 MPa / % or more, and particularly preferably 0.40 MPa / % or more. Furthermore, the absolute value range of the slope difference in this polyester film is, for example, about 0.20 to 1.10 MPa / %, preferably about 0.25 to 1.05 MPa / %, more preferably about 0.30 to 1.00 MPa / %, even more preferably about 0.35 to 0.95 MPa / %, and particularly preferably about 0.40 to 0.90 MPa / %.

[0130] The slope and absolute value of the difference between the yield point and the fracture point in the stress-strain curve can be determined with reference to JIS K 7161-1 (2014). Specifically, sample pieces are collected from polyester film, and the slopes of the stress-strain curves corresponding to the yield point and fracture point are measured using a tensile testing machine in both the longitudinal (MD) and transverse (TD) directions, referring to JIS K7161-1 (2014). The measurement conditions are 23°C, 50%RH atmosphere, 50mm chuck spacing between the sample pieces, and tensile speed of 200mm / min. Furthermore, the slopes of each stress-strain curve are calculated using the least squares method of the regression line. For the calculation conditions, the number of measurement points is set to 1 point every 0.1 seconds, and more than 100 data points are used.

[0131] It should be noted that the tensile yield stress and tensile elongation at break, as described below, can be controlled within the specified range, for example, by appropriately setting the mass ratio of polyethylene terephthalate to polybutylene terephthalate, the stretching ratio during film manufacturing, the preheating / stretching temperature, and the heat setting temperature.

[0132] As in this outer casing material, a polyester film containing polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) within a specific range of 65 / 35 to 90 / 10 is used as the substrate layer 1. Based on the outer casing material for the energy storage device, which is composed of at least the substrate layer 1, the barrier layer 5, and the heat-welding resin layer 6 in sequence, excellent formability can be achieved, and excellent heat resistance that can withstand heat welding can also be taken into account.

[0133] Furthermore, by using this polyester film containing polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) in a specific range of 65 / 35 to 90 / 10 and controlling the tensile elongation at break in the width direction (TD) within a specific range as the substrate layer 1, the outer casing material for the energy storage device, which is composed of at least the substrate layer 1, the polyamide layer 3, the barrier layer 5, and the heat-melting resin layer 6 in sequence, can achieve excellent formability and can highly balance excellent heat resistance that can withstand heat fusion.

[0134] Specifically, as with this outer packaging material, a substrate layer 1 comprising a polyester film containing polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) within a specific range of 65 / 35 to 90 / 10, and controlling the tensile elongation at break in the width direction (TD) within a specific range, is preferred. This substrate layer 1 also comprises a polyester film containing polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) within the same specific range of 65 / 35 to 90 / 10, and controlling the tensile yield stress and tensile elongation at break in both the length direction (MD) and width direction (TD) within specific ranges. This suppresses localized stress concentration during molding and promotes stress homogenization, thus preventing damage and, for example, allowing for the formation of deeper recesses than before during deep drawing. Furthermore, it also suppresses the degradation of the bag's surface appearance during heat sealing and the welding of the heat-sealing rod.

[0135] In this way, this outer casing material is very useful in terms of its excellent formability and heat resistance. For example, it can be used as an outer casing material for larger-sized, specifically deeper-recessed, energy storage devices. For example, by increasing the contents of each bag (volume of the housing) obtained by this outer casing material, the capacity / energy density of the battery per unit volume can be further improved.

[0136] The composition of this polyester film will be described in further detail below.

[0137] [Polyethylene terephthalate (PET)]

[0138] The polyethylene terephthalate constituting this polyester film can be a homopolymer polyethylene terephthalate formed solely from repeating units of polyethylene terephthalate, or it can be a copolymer polyethylene terephthalate with polyethylene terephthalate as the main repeating unit. This copolymer polyethylene terephthalate preferably contains 70 mol% or more of repeating units of polyethylene terephthalate, more preferably 80 mol% or more, and may also contain 90 mol% or more and 98 mol% or less. One of these can be used alone, or two or more can be used in combination.

[0139] In the copolymerization of polyethylene terephthalate, the monomers that are copolymerized include diacid components other than terephthalic acid and its lower alcohol esters, and diol components other than ethylene glycol. Examples of such diacid components include aromatic or aliphatic polybasic acids such as isophthalic acid, naphthalic acid, adipic acid, sebacic acid, trimellitic acid, and succinic acid, or their esters.

[0140] On the other hand, examples of diol components include alkylene glycols such as diethylene glycol, propylene glycol, butanediol, trimethylene glycol, hexamethylene glycol, neopentyl glycol, 1,4-cyclohexanediol, and 1,3-octanediol; aromatic alcohols such as bisphenol A and 4,4'-dihydroxybiphenyl; ethylene oxide diadducts of bisphenol A; and propylene oxide diadducts of bisphenol A.

[0141] Specifically, as a copolymer of polyethylene terephthalate, examples include copolymer polyesters (hereinafter abbreviated as poly(terephthalic acid / isophthalic acid) glycol ester, poly(terephthalic acid / adipic acid) glycol ester, poly(terephthalic acid / sodium sulfonate) glycol ester, poly(terephthalic acid / sodium isophthalate) glycol ester, poly(terephthalic acid / phenyl-dicarboxylic acid) glycol ester, and poly(terephthalic acid / decanedicarboxylic acid) glycol ester, etc., which are based on polyethylene terephthalate as the main body and polymerized with polyethylene isophthalate.

[0142] From the viewpoint of formability or heat resistance, the intrinsic viscosity of polyethylene terephthalate is preferably 0.50 dL / g or higher, more preferably 0.53 dL / g or higher, even more preferably 0.57 dL / g or higher, and particularly preferably 0.60 dL / g or higher. Furthermore, the intrinsic viscosity is preferably 1.00 dL / g or lower, more preferably 0.96 dL / g or lower, even more preferably 0.93 dL / g or lower, and particularly preferably 0.90 dL / g or lower. Moreover, regarding the preferred range of the intrinsic viscosity of polyethylene terephthalate, for example, it is preferably 0.50 to 1.00 dL / g, more preferably 0.53 to 0.96 dL / g, even more preferably 0.57 to 0.93 dL / g, and particularly preferably 0.60 to 0.90 dL / g. It should be noted that the intrinsic viscosity of polyethylene terephthalate can be appropriately set within the range mentioned above, and is not limited to the following values. For example, it can also be 0.60 to 0.80 dL / g, 0.60 to 0.75 dL / g, etc.

[0143] [Polybutylene terephthalate (PBT)]

[0144] The polybutylene terephthalate constituting this polyester film can be a homopolymer polybutylene terephthalate composed solely of repeating units of butylene terephthalate, or a copolymer polybutylene terephthalate with butylene terephthalate as the main repeating unit. This copolymer polybutylene terephthalate preferably contains 70 mol% or more of repeating units of butylene terephthalate, more preferably 80 mol% or more, and may also contain 90 mol% or more and 98 mol% or less. They can be used individually, or in combination of two or more.

[0145] In the copolymerization of polybutylene terephthalate, the monomers that are copolymerized may include, for example, diacid components other than terephthalic acid and its lower alcohol esters, and diol components other than 1,4-butanediol. Examples of such diacid components include aromatic or aliphatic polyacids, such as isophthalic acid, naphthalenedicarboxylic acid, adipic acid, sebacic acid, trimellitic acid, and succinic acid, or their esters.

[0146] On the other hand, examples of diol components include alkylene glycols such as ethylene glycol, diethylene glycol, propylene glycol, trimethylene glycol, hexamethylene glycol, neopentyl glycol, cyclohexanediol, and 1,3-octanediol; aromatic alcohols such as bisphenol A and 4,4'-dihydroxybiphenyl; ethylene oxide diadducts of bisphenol A; and alkyl oxide adducts such as propylene oxide diadducts of bisphenol A.

[0147] Specifically, as a copolymer of polybutylene terephthalate, examples include copolymer polyesters (hereinafter abbreviated as poly(terephthalic acid / isophthalic acid) butylene glycol, poly(terephthalic acid / adipic acid) butylene glycol, poly(terephthalic acid / sedipic acid) butylene glycol, poly(terephthalic acid / decanedicarboxylic acid) butylene glycol, etc., which are polymerized with butylene terephthalate as the main body and butylene isophthalate as the repeating unit.

[0148] From the viewpoint of formability or heat resistance, the intrinsic viscosity of polybutylene terephthalate is preferably 0.70 dL / g or higher, more preferably 0.73 dL / g or higher, even more preferably 0.77 dL / g or higher, and particularly preferably 0.80 dL / g or higher. Furthermore, the intrinsic viscosity is preferably 1.40 dL / g or lower, more preferably 1.37 dL / g or lower, even more preferably 1.33 dL / g or lower, and particularly preferably 1.30 dL / g or lower. Moreover, regarding the preferred range of the intrinsic viscosity of polybutylene terephthalate, for example, it is preferably 0.70 to 1.40 dL / g, more preferably 0.73 to 1.37 dL / g, even more preferably 0.77 to 1.33 dL / g, and particularly preferably 0.80 to 1.30 dL / g. It should be noted that the intrinsic viscosity of polybutylene terephthalate can be appropriately set within the range mentioned above, and is not limited to the following. For example, it can also be 0.80 to 1.20 dL / g, 0.80 to 1.10 dL / g, 0.80 to 1.00 dL / g, etc.

[0149] It should be noted that when using two or more polyethylene terephthalate (PET) or two or more butylene terephthalate (PET) with different intrinsic viscosities, the intrinsic viscosity refers to the intrinsic viscosity of these blended polyesters. Furthermore, the intrinsic viscosity can be measured according to JIS K7367-1:2002 using conventional methods. For example, an Ubbelohde viscometer can be used with phenol:tetrachloroethane = 1:1 as the solvent, and the measurement can be performed at 30°C.

[0150] Preferably, the polyester film constituting the substrate layer 1 may also contain other resin components, additives, and other components besides polyethylene terephthalate and polybutylene terephthalate, but polyethylene terephthalate is the main component. Furthermore, the total content of polyethylene terephthalate and polybutylene terephthalate relative to the total mass of the polyester film (i.e., the total mass of the substrate layer 1) is preferably 90% by mass or more, more preferably 95% by mass or more, and may also be 98% to 100% by mass.

[0151] Other resin components, additives, and other ingredients are not particularly limited and may include lubricants, flame retardants, antiblocking agents, antioxidants, light stabilizers, tackifiers, antistatic agents, and colorants. They may be used individually or in combination of two or more.

[0152] There are no particular limitations on the lubricant used, and examples include inorganic particles such as silica, alumina, titanium dioxide, calcium carbonate, kaolin, and barium sulfate; organic particles obtained by polymerizing acrylate monomers, styrene monomers, organosilicon monomers, etc.; organic particles obtained by copolymerizing these monomers; acrylic resin particles; melamine resin particles; organosilicon resin particles; cross-linked polystyrene particles, etc.

[0153] The average particle size of the lubricant is not particularly limited, but is generally 0.03 μm or more, preferably 0.1 μm or more, more preferably 0.3 μm or more, and even more preferably 0.6 μm or more. Furthermore, it is generally 10 μm or less, preferably 6 μm or less, more preferably 5 μm or less, and even more preferably 4 μm or less. Additionally, the range of the average particle size of the lubricant is generally 0.03 to 10 μm, preferably 0.1 to 6 μm, more preferably 0.3 to 5 μm, and even more preferably 0.6 to 4 μm.

[0154] It should be noted that, in this specification, the average particle size of the lubricant can be determined by observing more than 10 particles and measuring their diameters using a scanning electron microscope (SEM) or a transmission electron microscope (TEM), and then using this average value. In the case of non-spherical particles, the average of the longest and shortest diameters can be measured as the diameter of each particle.

[0155] In this polyester film, the content of the lubricant is not particularly limited, but is generally 0.001% by mass or more relative to the total mass of the polyester film, preferably 0.004% by mass or more, more preferably 0.008% by mass or more, and even more preferably 0.01% by mass or more. Furthermore, the content of the lubricant is 3% by mass or less, preferably 1.5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.7% by mass or less. The range of the lubricant content relative to the total mass of the polyester film is generally 0.001 to 3% by mass, preferably 0.004 to 1.5% by mass, more preferably 0.008 to 1% by mass, and even more preferably 0.01 to 0.7% by mass.

[0156] Furthermore, amide-based lubricants are preferred as lubricants. Examples include saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, hydroxymethyl amides, saturated fatty acid diamides, unsaturated fatty acid diamides, fatty acid ester amides, and aromatic diamides.

[0157] Examples of saturated fatty acid amides include lauryl amide, palmitamide, stearamide, behenamide, and hydroxystearamide. Examples of unsaturated fatty acid amides include oleamide and erucamide. Examples of substituted amides include N-oleopalmitamide, N-stearylstearamide, N-stearyloleamide, N-oleostearamide, and N-stearylerucamide. Furthermore, examples of hydroxymethyl amides include hydroxymethylstearamide. Examples of saturated fatty acid diamides include methylene bis-stearamide, ethylene bis-decanoamide, ethylene bis-laurateamide, ethylene bis-stearamide, ethylene bis-hydroxystearamide, ethylene bis-behenamide, hexamethylene bis-stearamide, hexamethylene bis-behenamide, hexamethylene hydroxystearamide, N,N'-distearate adipamide, and N,N'-distearate sebacamide. Examples of unsaturated fatty acid diamides include ethylene dioleamide, ethylene dierucamide, hexamethylene dioleamide, N,N'-dioleoyl adipamide, and N,N'-dioleoyl sebacate amide. Examples of fatty acid ester amides include stearamide ethyl stearate. Furthermore, examples of aromatic diamides include isophthalic acid bis-stearamide, isophthalic acid bis-hydroxy stearamide, and N,N'-distearate isophthalamide. They can be used alone or in combination of two or more.

[0158] When a lubricant is present on the surface of the polyester film, there is no particular limitation on its amount, for example, about 3 mg / m³. 2 The above is preferably about 4 mg / m³. 2 The above is approximately 5 mg / m². 2 That's all. Furthermore, the amount of lubricant present on the surface of this polyester film is, for example, about 15 mg / m³. 2 The following is preferred: approximately 14 mg / m³ 2 The following is approximately 10 mg / m² 2 The following applies. Furthermore, the preferred range for the amount of lubricant present on the surface of the substrate layer 1 is 3–15 mg / m³. 2 Approximately 3-14 mg / m² 2 Approximately 3-10 mg / m² 2 Approximately 4-15 mg / m² 2 Approximately 4-14 mg / m² 2 Approximately 4-10 mg / m² 2Approximately 5-15 mg / m² 2 Approximately 5-14 mg / m² 2 Approximately 5-10 mg / m² 2 The lubricant present on the surface of this polyester film can be formed by the seepage of lubricant contained in the resin constituting the polyester film, or it can be formed by coating the surface of the substrate layer 1 with lubricant.

[0159] This polyester film can be composed of a single layer or a laminate of two or more layers, preferably a laminate of three or more layers. There is no particular limit to the number of layers, but it is preferably around 10 layers or less. Examples of this polyester film composed of a laminate of two or more layers include layer structures such as "first layer (surface layer) / second layer (surface layer)" and "first layer (surface layer) / second layer (intermediate layer) / third layer (surface layer)". Among these, from the viewpoint of balancing formability and heat resistance, a polyester film composed of three layers ("first layer (surface layer) / second layer (intermediate layer) / third layer (surface layer)") is preferred. When the polyester film is configured as "first layer (surface layer) / second layer (intermediate layer) / third layer (surface layer)," it is preferable that the thickness of the second layer (intermediate layer) is greater than the thickness of the first layer (surface layer), more preferably that the thickness of the second layer (intermediate layer) is greater than the thickness of the third layer (surface layer), and even more preferably that the thickness of the second layer (intermediate layer) is greater than the thickness of both the first layer (surface layer) and the third layer (surface layer). From the viewpoint of balancing formability and heat resistance, the thickness ratio of each layer (first layer (surface layer): second layer (intermediate layer): third layer (surface layer)) is preferably 1.0–1.6: 8.0–12: 1.0–1.6, more preferably 1.0–1.5: 8.5–11.5: 1.0–1.5, and even more preferably 1.0–1.4: 9.0–11.0: 1.0–1.4.

[0160] Furthermore, when the polyester film is composed of two or more laminates, it is preferable that the material composition of the surface layer is different from the material composition of at least one of the other layers.

[0161] That is, for example, when the polyester film is a laminate comprising one surface layer, another surface layer, and one or more other layers located between the surface layers (layers other than the two surface layers in the laminate), it is preferable that the material composition of at least one of the other layers is different from the material composition of the surface layer. Furthermore, it is preferable that the material composition of all the other layers is different from the material composition of the surface layer, and more preferably that the material composition of all the other layers is different from the material composition of the surface layer and the other surface layer. Furthermore, when the polyester film is a laminate comprising one surface layer, another surface layer, and one or more other layers located between the surface layers (layers other than the two surface layers in the laminate), it is even more preferable that the material composition of all the other layers is different from the material composition of the surface layer and the other surface layer, and that the material composition of the surface layer and the other surface layer is the same.

[0162] Furthermore, when the polyester film is composed of two or more laminates, the material composition forming one surface layer can be different from that forming another surface layer. That is, when the polyester film has a two-layer structure of "first layer (surface layer) / second layer (surface layer)," two different two-layer structures are preferred. Specifically, it is preferable that the polyester film contains two layers, and that the materials forming these layers are of two different types, with the materials constituting the first layer (surface layer) and the second layer (surface layer) having different compositions.

[0163] Furthermore, when the polyester film is configured as "first layer (surface layer) / second layer (intermediate layer) / third layer (surface layer)," it is preferable that the material composition forming the second layer (intermediate layer) is different from that forming the first layer (surface layer), more preferably that the material composition forming the second layer (intermediate layer) is different from that forming the third layer (surface layer), more preferably that the material composition forming the second layer (intermediate layer) is different from that forming the first layer (surface layer) and the third layer (surface layer), and even more preferably that the material composition forming the second layer (intermediate layer) is different from that forming the first layer (surface layer) and the third layer (surface layer), while the material compositions forming the first layer (surface layer) and the third layer (surface layer) are the same. Additionally, when the polyester film is configured as "first layer (surface layer) / second layer (intermediate layer) / third layer (surface layer)," two three-layer structures are preferred. Specifically, it is preferable that the polyester film contains three layers, that the materials forming these layers are of two types, and that the material compositions constituting the first layer (surface layer) and the third layer (surface layer) are the same.

[0164] It should be noted that "different material composition" means that the material composition is not the same or substantially different. "Substantially different" means that, when comparing the components that make up each material, the difference in the content of each component exceeds ±1% by mass, or / and, in the case of containing dissimilar components, the total content of the dissimilar components relative to the whole material is more than 2% by mass.

[0165] It should be noted that, when the polyester film is composed of a single layer, the mass ratio (PET / PBT) of the entire single layer is preferably within the specified range; when the polyester film is composed of a laminate, the mass ratio (PET / PBT) of the entire laminate is preferably within the specified range. It should also be noted that, when the polyester film is composed of a laminate, the mass ratio (PET / PBT) of a portion of the layers constituting the laminate may be outside the specified range; alternatively, the mass ratio (PET / PBT) of all the layers constituting the laminate may be within the specified range.

[0166] Furthermore, this polyester film, consisting of two or more layers, can be formed by co-extruding a specified raw material to create a laminate of two or more layers, or it can be formed by laminating single-layer polyester films using an adhesive or the like. Additionally, this polyester film, consisting of two or more layers, can have a structure where the polyester layers constituting each layer are directly connected, or it can have a structure where an adhesive layer is provided between the polyester layers constituting each layer. Specifically, in layer structures such as "first layer (surface layer) / second layer (surface layer)" or "first layer (surface layer) / second layer (intermediate layer) / third layer (surface layer)", the laminations can be: a lamination where the first layer (surface layer) and the second layer (surface layer) are directly connected; a lamination where one side of the second layer (intermediate layer) is directly connected to the first layer (surface layer) and the other side of the second layer (surface layer) is directly connected to the third layer (surface layer); or a lamination with an adhesive layer between the first layer (surface layer) and the second layer (surface layer); or a lamination with an adhesive layer between one side of the second layer (intermediate layer) and the first layer (surface layer) and the other side of the second layer (intermediate layer) and the third layer (surface layer). The adhesive layer can be anything that bonds the layers together; there are no particular restrictions. Appropriate adhesives can be selected from those exemplified in the examples of the first adhesive layer 2, the second adhesive layer 4, and the third adhesive layer described later.

[0167] In a preferred embodiment of this polyester film, in a polyester film composed of two or more laminates, from the viewpoint of effectively suppressing the welding of the heat-sealing rod used in heat fusion welding, the content of polyethylene terephthalate contained in at least one or two of the surface layers is preferably 65% ​​by mass or more, 66% by mass or more, 67% by mass or more, more preferably 68% by mass or more, 69% by mass or more, and even more preferably 70% by mass or more, 71% by mass or more, relative to the total amount of material constituting the surface layer. Alternatively, it may be 100% by mass, preferably 97% by mass or less, 93% by mass or less, 90% by mass or less, 85% by mass or less, 83% by mass or less, more preferably 82% by mass or less, and even more preferably 80% by mass or less. Furthermore, the range of polyethylene terephthalate content contained in the surface layer is preferably 65-85% by mass, 66-85% by mass, more preferably 68-82% by mass, and even more preferably 70-80% by mass.

[0168] As an embodiment of this polyester film, from the viewpoint of suppressing the reduction in surface appearance caused by surface whitening during heat fusion by improving heat resistance and suppressing the welding of the laminate to the heat-sealing rod used in heat fusion, in this polyester film composed of two or more laminates, and further in this polyester film having a surface layer, an intermediate layer, and a top layer in sequence, it is preferable that at least one or two of the surface layers contain polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 100 / 0 to 90 / 10 (polyethylene terephthalate / polybutylene terephthalate), more preferably about 100 / 0 to 91 / 9, and even more preferably about 100 / 0 to 92 / 8. Furthermore, this surface layer is preferably present on the outermost side of the outer casing material for the energy storage device.

[0169] As an embodiment of this polyester film, from the viewpoint of suppressing the reduction in surface appearance caused by surface whitening during hot-melt welding by improving heat resistance and suppressing the welding of the laminate to the heat-sealing rod used in hot-melt welding, in this polyester film composed of two or more laminates, and further in this polyester film having a surface layer, an intermediate layer, and a top layer in sequence, the content of polyethylene terephthalate contained in at least one or two surface layers is preferably 65% ​​by mass or more, 66% by mass or more, 67% by mass or more, more preferably 68% by mass or more, 69% by mass or more, and even more preferably 70% by mass or more, 71% by mass or more, relative to the total amount of material constituting the surface layer. Furthermore, it is preferably 85% by mass or less, 83% by mass or less, more preferably 82% by mass or less, and even more preferably 80% by mass or less. Furthermore, the range of the content of polyethylene terephthalate contained in the surface layer is preferably 65-85% by mass, 66-85% by mass, more preferably 68-82% by mass, and even more preferably 70-80% by mass.

[0170] As an embodiment of this polyester film, from the viewpoint of suppressing the reduction in surface appearance caused by surface whitening during heat fusion by improving heat resistance and suppressing the welding of the laminate to the heat-sealing bar used in heat fusion, in this polyester film composed of two or more laminates, the content of polyethylene terephthalate in one surface layer is preferably greater than the content of polyethylene terephthalate in at least one of the other layers, and more preferably greater than the content of polyethylene terephthalate in all of the other layers. Furthermore, the surface layer with a higher content of polyethylene terephthalate is preferably present on the outermost layer side of the outer casing material for the energy storage device. Specifically, for example, in the case where this polyester film has a two-layer structure of "first layer (surface layer) / second layer (surface layer)," it is preferable that the content of polyethylene terephthalate in one surface layer is greater than the content of polyethylene terephthalate in the other surface layer.

[0171] Furthermore, in this polyester film comprising a surface layer, an intermediate layer, and another surface layer in sequence, it is preferable that the content of polyethylene terephthalate in at least one or two surface layers is greater than the content of polyethylene terephthalate in the intermediate layer.

[0172] That is, in the polyester film composed of two or more laminates, the content (mass%) of polyethylene terephthalate relative to the total amount of material constituting one surface layer of the polyester film is preferably greater than the content (mass%) of polyethylene terephthalate relative to the total amount of material constituting at least one of the other layers or the content (mass%) of polyethylene terephthalate relative to the total amount of material constituting all the other layers.

[0173] For example, the difference between the total content (mass%) of polyethylene terephthalate relative to the total content (mass%) of the material constituting one surface layer of the polyester film and the total content (mass%) of polyethylene terephthalate relative to the total content (mass%) of each material constituting the other layers (polyethylene terephthalate content (mass%) - polyethylene terephthalate content (mass%) relative to the total content (mass%) of each material constituting the other layers) is, for example, about 3 to 30% by mass, preferably about 5 to 25% by mass, and more preferably about 10 to 20% by mass.

[0174] Furthermore, in this polyester film comprising a surface layer, an intermediate layer, and a surface layer in sequence, the content (mass%) of polyethylene terephthalate relative to the total amount of material constituting one surface layer of the polyester film is preferably greater than the content (mass%) of polyethylene terephthalate relative to the total amount of material constituting the intermediate layer. For example, the difference between the content (mass%) of polyethylene terephthalate relative to the total amount of material constituting one surface layer of the polyester film and the content (mass%) of polyethylene terephthalate relative to the total amount of material constituting the intermediate layer (content (mass%) of polyethylene terephthalate relative to the total amount of material constituting the surface layer - content (mass%) of polyethylene terephthalate relative to the total amount of material constituting the intermediate layer) is, for example, about 3 to 30% by mass, preferably about 5 to 25% by mass, and more preferably about 10 to 20% by mass.

[0175] In cases where the polyester film is composed of two or more laminates, in cases where it is composed of a laminate having a top layer, an intermediate layer, and a top layer in sequence, especially in cases where the composition of the materials constituting each layer is different, and in cases where the content of polyethylene terephthalate in the top layer is higher than the content of polyethylene terephthalate in at least one of the other layers, especially when the content of polyethylene terephthalate in the top layer is higher than the content of polyethylene terephthalate in the intermediate layer, it is not easy to adjust the various tensile properties such as elongation at break to the desired range. However, through in-depth research by the inventors, as described below, for example, by appropriately adjusting the mass ratio of polyethylene terephthalate to polybutylene terephthalate, the stretching ratio during film manufacturing, the preheating / stretching temperature, the heat setting temperature, etc., it is possible to control various tensile properties within the desired range. Furthermore, when the polyester film is composed of two or more laminates, when it is composed of a laminate having a top layer, an intermediate layer, and a top layer in sequence, especially when the composition of the materials constituting each layer is different, and when the content of polyethylene terephthalate in the top layer is higher than that in at least one of the other layers, especially when the content of polyethylene terephthalate in the top layer is higher than that in the intermediate layer, it is easier to balance the excellent formability and excellent heat resistance of the outer material to withstand heat welding.

[0176] The thickness (total thickness) of this polyester film is not particularly limited, but is, for example, about 4 μm or more, about 6 μm or more, preferably about 8 μm or more, more preferably about 10 μm or more, and even more preferably about 12 μm or more or about 15 μm or more. Furthermore, the thickness (total thickness) of this polyester film is, for example, about 100 μm or less, about 60 μm or less, about 40 μm or less, preferably about 30 μm or less, more preferably about 28 μm or less, and even more preferably about 26 μm or less. The preferred range for the thickness (total thickness) of this polyester film is, for example, approximately 4–100 μm, 6–100 μm, 8–100 μm, 10–100 μm, 12–100 μm, 15–100 μm, 4–60 μm, 6–60 μm, 8–60 μm, 10–60 μm, 12–60 μm, 15–60 μm, 4–40 μm, 6–40 μm, 8–40 μm, 10–40 μm, 12–40 μm. Approximately 1.5 μm, 15–40 μm, 4–30 μm, 6–30 μm, 8–30 μm, 10–30 μm, 12–30 μm, 15–30 μm, 4–28 μm, 6–28 μm, 8–28 μm, 10–28 μm, 12–28 μm, 15–28 μm, 4–26 μm, 6–26 μm, 8–26 μm, 10–26 μm, 12–26 μm, 15–26 μm.

[0177] When the polyester film is a laminate of two or more layers, there is no particular limitation on the thickness of the resin film constituting each layer. For example, it is about 1 μm or more, preferably about 1.5 μm or more, and also, for example, about 25 μm or less, preferably about 22 μm or less. The range of the thickness of the resin film constituting each layer is, for example, about 1 to 25 μm, preferably about 1.5 to 22 μm.

[0178] Specifically, there are no particular limitations. For example, in the case of this polyester film consisting of three layers: a first layer (surface layer), a second layer (intermediate layer), and a third layer (surface layer), it is preferred that the first layer (surface layer) and the third layer (surface layer) have a thickness of 1 μm or more and 2.8 μm or less, and 1.8 μm or more and 2.6 μm or less, respectively, and that the second layer (intermediate layer) has a thickness of 15 μm or more and 23 μm or less, and 18 μm or more and 22 μm or less, respectively.

[0179] Furthermore, when the polyester film is a laminate of two or more layers, it is preferable to manufacture a laminate with two layers having different properties. Based on this laminate, each layer can have different characteristics, thus achieving multi-functionality. Specifically, there are no particular limitations; for example, if the polyester film is composed of a three-layer laminate consisting of a surface layer, an intermediate layer, and a third layer, layers containing inorganic particles such as silica, organic particles, or additives such as lubricants can be formed on one or both of the surface layers, making the surface layer and the intermediate layer have different properties, thereby achieving multi-functionality.

[0180] In addition, from the perspective of adhesion and printability, a coating can be further formed on the surface of this polyester film.

[0181] There are no particular limitations. For example, a coating can be formed on the surface of the polyester film on the side of the barrier layer 5, or more specifically on the surface of the polyester film on the side of the first adhesive layer 2, which can improve interlayer adhesion.

[0182] The coating thickness is, for example, about 0.01 to 1.0 μm, and the coating weight is 0.005 to 1 g / m². 2 The concentration is approximately 0.01–0.6 g / m³, preferably 0.01–0.6 g / m³. 2 Approximately, more preferably 0.02–0.3 g / m 2 Left and right. This coating can be formed, for example, by an adhesive such as that exemplified in the first adhesive layer 2 described later.

[0183] Furthermore, without particular limitations, for example, a coating can be formed on the surface of the polyester film opposite to the barrier layer 5, or more specifically, on the surface of the polyester film opposite to the first adhesive layer 2, which can also improve printability. In addition, it can also improve heat resistance and reduce the likelihood of problems such as reduced surface appearance due to surface whitening during heat fusion and problems with the heat sealing bar used in heat fusion of the laminate.

[0184] The thickness of the coating is, for example, about 0.01 to 0.7 μm, preferably about 0.01 to 0.4 μm, and more preferably about 0.1 to 0.2 μm. The coating weight is, for example, 0.005 to 1 g / m². 2 The concentration is approximately 0.01–0.6 g / m³, preferably 0.01–0.6 g / m³. 2 The concentration is approximately 0.02–0.3 g / m³, with a further preferred value of 0.02–0.3 g / m³. 2 The concentration is approximately 0.03–0.1 g / m³, and more preferably 0.03–0.1 g / m³. 2 about.

[0185] The coating is not particularly limited and can be formed from various synthetic resins such as polyvinylidene chloride, vinylidene chloride-vinyl chloride copolymer, polyolefins, acid-modified polyolefins, polyesters, epoxy resins, phenolic resins, fluoropolymers, cellulose esters, polyurethanes, acrylic resins, and polyamides. They can be used individually or in combination of two or more. Furthermore, to improve sliding properties, the coating may contain lubricants as needed.

[0186] In the case of a coating formed for the purpose of improving heat resistance, it is preferable that the coating contains a release agent and a crosslinking agent.

[0187] There are no particular limitations on the release agent used; conventionally known compounds can be used. Examples of release agents include compounds containing long-chain alkyl groups, waxes, fluorinated compounds, and organosilicon compounds. Among these, at least one of compounds containing long-chain alkyl groups and waxes is preferred, and compounds containing long-chain alkyl groups are more preferred. A single release agent can be used, or two or more can be used in combination.

[0188] Compounds containing long-chain alkyl groups refer to compounds having straight-chain or branched alkyl groups with a carbon number of 6 or more, preferably 8 or more, and more preferably 12 or more. Examples of alkyl groups include hexyl, octyl, decyl, lauryl, octadecyl, and behenyl. Examples of compounds containing alkyl groups include various polymers containing long-chain alkyl groups, amines containing long-chain alkyl groups, ethers containing long-chain alkyl groups, and quaternary ammonium salts containing long-chain alkyl groups. Considering heat resistance and staining properties, polymers are preferred. Furthermore, from the viewpoint of efficiently obtaining mold release properties, polymers with long-chain alkyl groups on the side chains are more preferred.

[0189] Polymers with long-chain alkyl groups on their side chains can be obtained by reacting a polymer with a reactive group with a compound having an alkyl group capable of reacting with that reactive group. Examples of such reactive groups include hydroxyl, amino, carboxyl, and acid anhydride groups.

[0190] Examples of compounds containing these reactive groups include polyvinyl alcohol, polyethyleneimine, polyethyleneamine, polyester resins containing reactive groups, and poly(meth)acrylic acid resins containing reactive groups. Among these, polyvinyl alcohol is preferred considering its mold release properties and ease of handling.

[0191] Compounds containing alkyl groups capable of reacting with the aforementioned reactive groups include, for example, long-chain alkyl-containing isocyanates such as hexyl isocyanate, octyl isocyanate, decyl isocyanate, lauryl isocyanate, octadecyl isocyanate, and behenyl isocyanate; long-chain alkyl-containing acyl chlorides such as hexanoyl chloride, octanoyl chloride, decanoyl chloride, lauroyl chloride, octadecanoyl chloride, and behenyl chloride; long-chain alkyl-containing amines; and long-chain alkyl-containing alcohols. Among these, long-chain alkyl-containing isocyanates are preferred, and octadecyl isocyanate is particularly preferred, considering demolding properties and ease of handling.

[0192] Furthermore, polymers with long-chain alkyl side chains can also be obtained through polymers of long-chain alkyl methacrylates or copolymerization of long-chain alkyl methacrylates with other vinyl-containing monomers. Examples of long-chain alkyl methacrylates include hexyl methacrylate, octyl methacrylate, decyl methacrylate, lauryl methacrylate, octadecyl methacrylate, and behenyl methacrylate.

[0193] In addition to compounds containing long-chain alkyl groups, various other conventionally known release agents can also be used. Examples of conventionally known release agents include waxes, fluorinated compounds, and organosilicon compounds. However, from the viewpoint of oligomer precipitation, it is ideal that the coating of the present invention is formed from a release agent that is not an organosilicon compound. "Formed from a release agent that is not an organosilicon compound" means that the content of the organosilicon compound in the coating is preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 1% by mass or less, particularly preferably 0.5% by mass or less, and most preferably not intentionally contained. It is believed that even without the active use of organosilicon compounds, contaminants from foreign matter and dirt adhering to the production line and equipment in the membrane manufacturing process may be introduced.

[0194] Organosilicon compounds are compounds that have an organosilicon structure within their molecules. Examples include organosilicon emulsions, acrylic-grafted organosilicon, organosilicon-grafted acrylic acid, amino-modified organosilicon, perfluoroalkyl-modified organosilicon, and alkyl-modified organosilicon.

[0195] The content of the release agent is not particularly limited, but from the viewpoint of release performance and strength, it is, for example, 5 to 97% by mass relative to all non-volatile components of the coating, preferably 10 to 95% by mass, more preferably 20 to 90% by mass, even more preferably 30 to 80% by mass, and even more preferably 40 to 70% by mass.

[0196] When using a compound containing long-chain alkyl groups as a release agent, there is no particular limitation on its content. From the viewpoint of release performance, strength and heat resistance, it is preferably 30 to 95% by mass, more preferably 40 to 90% by mass, further preferably 45 to 85% by mass, and particularly preferably 50 to 80% by mass, relative to all non-volatile components of the coating.

[0197] Crosslinking agents can improve the strength, adhesion to the substrate, and heat resistance of coatings. Examples of crosslinking agents include melamine compounds, isocyanate compounds, oxazoline compounds, epoxy compounds, and carbodiimide compounds. Among these, melamine compounds or isocyanate compounds are preferred from the viewpoint of good film strength. Furthermore, melamine compounds are preferred from the viewpoint of excellent mold release properties, and isocyanate compounds are particularly preferred from the viewpoint of excellent heat resistance. In addition, two or more of these crosslinking agents can be used in combination.

[0198] Melamine compounds refer to compounds having a melamine backbone, such as hydroxyalkylated melamine derivatives, compounds formed by partially or completely etherifying hydroxyalkylated melamine derivatives with an alcohol, and mixtures thereof. Examples of hydroxyalkylation include hydroxymethylation, hydroxyethylation, hydroxyisopropylation, hydroxyn-butylation, and hydroxyisobutylation. From a reactivity point of view, hydroxymethylation is preferred. Furthermore, methanol, ethanol, isopropanol, n-butanol, and isobutanol are preferred alcohols used in etherification. From the viewpoint of improving coating strength and adhesion between the coating and the polyester film, partially etherified hydroxyalkylated melamine derivatives are preferred, and more preferably, hydroxyalkylated melamine etherified with methanol. Therefore, a more preferred method is partially etherified melamine having both hydroxymethyl and methoxymethyl groups. The amount of etherified hydroxyalkyl group relative to the unetherified hydroxyalkyl group is preferably 0.5 to 5 equivalents, more preferably 0.7 to 3 equivalents. Furthermore, the melamine compound can be any one of a monomer, a dimer or more polymers, or a mixture thereof. Additionally, substances such as urea co-condensed in a portion of the melamine can be used, and a catalyst can be used to improve the reactivity of the melamine compound.

[0199] Isocyanate compounds refer to isocyanates, or compounds with isocyanate derivative structures, such as terminated isocyanates, wherein the terminated isocyanate has a structure in which the isocyanate group of the isocyanate compound serving as a precursor is protected by a terminating agent. Examples of isocyanates include aliphatic isocyanate compounds, alicyclic isocyanate compounds, and aromatic isocyanate compounds. From the viewpoint of achieving higher reactivity and improving the heat resistance of the coating, these isocyanate compounds are more preferably compounds having multiple isocyanate groups, i.e., polyisocyanate compounds. Furthermore, when using an aqueous coating solution, terminated isocyanates are more preferred.

[0200] Examples of aliphatic polyisocyanate compounds include polyisocyanate compounds derived from aliphatic diisocyanates such as tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethyl-1,6-diisocyanate hexane, and lysine diisocyanate; lysine triisocyanate; 4-isocyanate methyl-1,8-octamethylene diisocyanate; bis(2-isocyanate ethyl)-2-isocyanate glutarate; or compounds derived from these isocyanate compounds. Among these, hexamethylene diisocyanate is preferred from the viewpoint of ease of industrial acquisition.

[0201] Examples of alicyclic polyisocyanate compounds include isophorone diisocyanate, 1,3-bis(isocyanate-methyl)-cyclohexane, 4,4'-dicyclohexylmethane diisocyanate, norbornene diisocyanate, hydrogenated diphenylmethylene diisocyanate, or compounds derived from these isocyanates. Among these, isophorone diisocyanate is preferred from the perspectives of weather resistance and ease of industrial acquisition.

[0202] Examples of aromatic polyisocyanate compounds include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, naphthalene diisocyanate, phenylmethylene diisocyanate, or compounds derived from these isocyanates.

[0203] Among these polyisocyanate compounds, aliphatic and alicyclic polyisocyanate compounds are preferred due to their excellent weather resistance. Furthermore, among aliphatic polyisocyanate compounds, aliphatic polyisocyanate compounds derived from aliphatic diisocyanates are preferred. Hexamethylene diisocyanate is particularly preferred. Moreover, these isocyanate compounds can be used alone or in combination of two or more.

[0204] End-capped polyisocyanate compounds can be synthesized by reacting the isocyanate groups of the polyisocyanate compound with an end-capping agent.

[0205] Examples of end-capping agents include active methylene-based, oxime-based, pyrazole-based, alcohol-based, alkylphenol-based, phenol-based, thiol-based, amide-based, imide-based, imidazole-based, urea-based, amine-based, imine-based, and bisulfite-based end-capping agents. Among these, active methylene-based end-capping agents are preferred, especially considering that their exfoliation properties are less likely to change after heating. Furthermore, two or more of these end-capping agents may be used in combination.

[0206] Examples of active methylene-based capping agents include isobutyryl acetate, n-propionyl acetate, n-butyryl acetate, n-valeryl acetate, n-hexanoyl acetate, 2-ethylheptanoyl acetate, malonic acid ester, acetoacetate, and acetylacetone. Among these, isobutyryl acetate, n-propionyl acetate, n-butyryl acetate, n-valeryl acetate, n-hexanoyl acetate, and 2-ethylheptanoyl acetate are preferred from the perspective of excellent low-temperature curing properties and storage stability in the presence of water; more preferably isobutyryl acetate, n-propionyl acetate, and n-valeryl acetate; and even more preferably isobutyryl acetate. More specifically, examples of isobutyryl acetate esters include methyl isobutyryl acetate, ethyl isobutyryl acetate, n-propyl isobutyryl acetate, isopropyl isobutyryl acetate, n-butyl isobutyryl acetate, isobutyl isobutyryl acetate, tert-butyl isobutyryl acetate, n-pentyl isobutyryl acetate, n-hexyl isobutyryl acetate, 2-ethylhexyl isobutyryl acetate, phenyl isobutyryl acetate, and benzyl isobutyryl acetate. Among these, methyl isobutyryl acetate and ethyl isobutyryl acetate are preferred. Examples of n-propionyl acetate esters include methyl n-propionyl acetate, ethyl n-propionyl acetate, isopropyl n-propionyl acetate, n-butyl n-propionyl acetate, and tert-butyl n-propionyl acetate. Among these, methyl n-propionyl acetate and ethyl n-propionyl acetate are preferred. Examples of n-valeroyl acetate esters include methyl n-valeroyl acetate, ethyl n-valeroyl acetate, isopropyl n-valeroyl acetate, n-butyl n-valeroyl acetate, and tert-butyl n-valeroyl acetate. Among these, methyl n-valeroyl acetate and ethyl n-valeroyl acetate are preferred.

[0207] In the active methylene-terminated isocyanate compounds used in the coating, the active methylene-based terminator described above can be used alone, or two or more can be used in combination. As active methylene-based terminators used in combination, dimethyl malonate and diethyl malonate are preferred from the perspectives of excellent low-temperature curing properties and excellent heat resistance of the resulting coating.

[0208] Examples of oxime-type capping agents include formaldehyde oxime, acetaldehyde oxime, acetone oxime, methyl ethyl ketone oxime, and cyclohexanone oxime.

[0209] Examples of pyrazole-based end-capping agents include pyrazole, 3-methylpyrazole, and 3,5-dimethylpyrazole. Examples of alcohol-based end-capping agents include methanol, ethanol, 2-propanol, n-butanol, sec-butanol, 2-ethyl-1-hexanol, 2-methoxyethanol, 2-ethoxyethanol, and 2-butoxyethanol.

[0210] Examples of alkylphenol end-capping agents include monoalkylphenols such as n-propylphenol, isopropylphenol, n-butylphenol, sec-butylphenol, tert-butylphenol, n-hexylphenol, 2-ethylhexylphenol, n-octylphenol, and n-nonylphenol, as well as dialkylphenols such as di-n-propylphenol, diisopropylphenol, isopropylcresol, di-n-butylphenol, di-tert-butylphenol, di-sec-butylphenol, di-n-octylphenol, di-2-ethylhexylphenol, and di-n-nonylphenol.

[0211] Examples of phenolic end-capping agents include phenol, cresol, ethylphenol, styrene-modified phenol, and hydroxybenzoic acid esters.

[0212] Examples of thiol-based end-capping agents include butyl mercaptan and dodecyl mercaptan.

[0213] Examples of amide-based end-capping agents include acetanilide, acetamide, ε-caprolactam, δ-valerolactam, and γ-butyrolactam.

[0214] Examples of imide-based end-capping agents include succinimide and maleimide.

[0215] Examples of imidazole-based capping agents include imidazole and 2-methylimidazole.

[0216] Examples of urea-based end-capping agents include urea, thiourea, and ethylidene urea.

[0217] Examples of amine-based end-capping agents include diphenylamine, aniline, carbazole, di-n-propylamine, diisopropylamine, and isopropyl ethylamine. Examples of imine-based end-capping agents include ethyleneimine and polyethyleneimine.

[0218] The end-capped isocyanate compound used in the coating preferably contains a hydrophilic site. As a method for adding a hydrophilic site to the end-capped isocyanate compound, for example, a method can be listed whereby the isocyanate group of the isocyanate compound as a precursor reacts with a hydrophilic compound having active hydrogen.

[0219] Hydrophilic compounds with active hydrogen that are used as end-capped isocyanate compounds in coatings include, for example, polyethylene glycol compounds, carboxylic acid compounds, sulfonic acid compounds, and amine compounds. These hydrophilic compounds can be used alone or in combination of two or more.

[0220] Examples of polyethylene glycol compounds include monoalkoxy polyethylene glycol, polyethylene glycol, polyoxypropylene-polyoxyethylene copolymer diol, and polyoxypropylene-polyoxyethylene block polymer diol. Among these, monoalkoxy polyethylene glycol, monomethoxy polyethylene glycol, and monoethoxy polyethylene glycol are particularly preferred.

[0221] Examples of compounds containing a carboxylic acid group include monohydroxycarboxylic acids, dihydroxycarboxylic acids, or their derivatives. Among compounds containing a carboxylic acid group, monohydroxycarboxylic acids or dihydroxycarboxylic acids are preferred, and monohydroxycarboxylic acids are more preferred.

[0222] Specific examples of compounds containing carboxylic acid groups include hydroxypentanoic acid, 2,2-dimethylolpropionic acid, 2,2-dimethylolbutyric acid, or derivatives of polycaprolactone diol, polyether polyols, etc., and their salts, which use these as initiators.

[0223] Examples of compounds containing sulfonic acid groups include aminoethylsulfonic acid, ethylenediamine-propyl-β-ethylsulfonic acid, 1,3-propanediamine-β-ethylsulfonic acid, and N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid.

[0224] As amine-containing compounds, examples include amine compounds containing hydroxyl groups. Specifically, examples include dimethylethanolamine and diethylethanolamine.

[0225] Oxazoline compounds are compounds containing an oxazoline group within their molecules. Polymers containing an oxazoline group are particularly preferred and can be prepared by homopolymerization of monomers containing addition-polymerizable oxazoline groups or by polymerization with other monomers. Examples of monomers containing addition-polymerizable oxazoline groups include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline. One or a mixture of two or more of these monomers can be used.

[0226] Of these, 2-isopropenyl-2-oxazoline is readily available industrially and is the preferred choice.

[0227] Other monomers are acceptable as long as they can copolymerize with monomers containing addition-polymerizable oxazoline groups; there are no restrictions. Examples include (meth)acrylates such as alkyl methacrylates (alkyl groups being methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, cyclohexyl); unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, styrene sulfonic acid and their salts (sodium salts, potassium salts, ammonium salts, tertiary amine salts, etc.); unsaturated nitriles such as acrylonitrile and methacrylonitrile; and (methyl) Unsaturated amides such as acrylamide, N-alkyl (methyl)acrylamide, and N,N-dialkyl (methyl)acrylamide (alkyl groups being methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, cyclohexyl, etc.); vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α,β-unsaturated monomers such as vinyl chloride and vinylidene chloride; and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene. One or more of these monomers may be used.

[0228] Epoxy compounds are compounds that have epoxy groups in their molecules. Examples include epichlorohydrin and ethylene glycol, polyethylene glycol, glycerol, polyglycerol, bisphenol A and other condensates with hydroxyl and amino groups. These include polyepoxy compounds, diepoxy compounds, monoepoxy compounds, glycidylamine compounds, etc.

[0229] Examples of polyepoxide compounds include sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, triglycidyl tris(2-hydroxyethyl) isocyanate, glycerol polyglycidyl ether, and trimethylolpropane polyglycidyl ether. Examples of diepoxide compounds include neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, and ethylene glycol diglycidyl ether. Glyceryl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, and polytetramethylene glycol diglycidyl ether are examples of monoepoxide compounds, such as allyl glycidyl ether, 2-ethylhexyl glycidyl ether, and phenyl glycidyl ether. As glycidylamine compounds, examples include N,N,N',N'-tetraglycidyl-m-phenylenediamine and 1,3-bis(N,N-diglycidylamino)cyclohexane.

[0230] The content of the crosslinking agent is not particularly limited, but from the viewpoint of demolding performance and strength, it is, for example, 3 to 80% by mass relative to all non-volatile components of the coating, preferably 5 to 70% by mass, more preferably 10 to 60% by mass, and even more preferably 15 to 50% by mass.

[0231] When using melamine compounds as crosslinking agents, there are no particular limitations on their content. From the viewpoint of release performance, strength, and heat resistance, the content is preferably 5 to 70% by mass, more preferably 10 to 60% by mass, and particularly preferably 15 to 50% by mass, relative to all non-volatile components of the coating.

[0232] In embodiments of this polyester film, from the viewpoints of improving heat resistance, suppressing the reduction in surface appearance caused by surface whitening during heat fusion, and effectively suppressing the welding of the heat-sealing rod used in heat fusion, the coating preferably contains, for example, a compound containing long-chain alkyl groups and a melamine compound, and more preferably, the main components of the coating are a compound containing long-chain alkyl groups and a melamine compound. That is, the total content of the compound containing long-chain alkyl groups and the melamine compound relative to all non-volatile components of the coating is 60% by mass or more, preferably 65% ​​by mass or more, more preferably 70% by mass or more, even more preferably 80 to 100% by mass, and particularly preferably 90 to 100% by mass.

[0233] Furthermore, from the same viewpoint, the coating preferably contains a long-chain alkyl compound and a melamine compound in a mass ratio of, for example, 95 / 5 to 5 / 95 (compound containing long-chain alkyl compounds / melamine compounds), more preferably 90 / 10 to 10 / 90, even more preferably 80 / 20 to 20 / 80, and particularly preferably 70 / 30 to 30 / 70.

[0234] As an embodiment of this outer casing material, from the same viewpoint, it is preferable to provide an outer casing material for an energy storage device composed of a laminate having a coating containing a compound containing long-chain alkyl groups and a melamine compound as a substrate layer, and sequentially comprising the substrate layer, a barrier layer, and a heat-melting resin layer for accommodating an energy storage device on the side of the heat-melting resin layer.

[0235] There are no particular limitations on the method of forming the coating. Conventional methods can be used appropriately. Preferably, the specified material is coated onto a polyester film, and then dried, cured, or heat-treated as needed to form the coating. There are no particular limitations on the coating method. Conventional coating methods such as reverse gravure coating, direct gravure coating, roller coating, mold coating, bar coating, and curtain coating can be used.

[0236] As the polyester film, a stretched film is preferred, for example, uniaxial stretched film and biaxial stretched film, with biaxial stretched film being the most preferred. As the stretching method for forming the biaxial stretched film, examples include successive biaxial stretching, blown film method, and simultaneous biaxial stretching, with successive biaxial stretching being the most preferred.

[0237] It should be noted that biaxially stretched film refers to a film in which the refractive index in the longitudinal (MD) and width (TD) directions is higher than the refractive index in the thickness direction. It is usually obtained by stretching the film along the longitudinal and width directions.

[0238] When the polyester film is a biaxially stretched film, the product of the stretch ratio in the width direction (TD) and the stretch ratio in the length direction (MD) (stretch ratio in the width direction (TD) × stretch ratio in the length direction (MD)) is preferably greater than 15.5, more preferably 15.6 or more, and even more preferably 15.7 or more. It should be noted that there is no particular upper limit to the product of the stretch ratio in the width direction (TD) and the stretch ratio in the length direction (MD) of the polyester film; for example, it can be 19.5 or less, 19.3 or less, 19.0 or less, or 18.7 or less.

[0239] When the polyester film is a biaxially stretched film, the difference between the stretch ratio in the width direction (TD) and the stretch ratio in the length direction (MD) (stretch ratio in the width direction - stretch ratio in the length direction) is preferably 0.3 times or more, more preferably 0.4 times or more, even more preferably 0.5 times or more, and even more preferably 0.6 times or more. It should be noted that there is no particular upper limit to the difference between the stretch ratio in the width direction and the stretch ratio in the length direction of the polyester film; for example, it can be 2.0 times or less, 1.8 times or less, 1.6 times or less, or 1.4 times or less.

[0240] When the polyester film is a biaxially stretched film, the ratio of the stretch ratio in the width direction to the stretch ratio in the length direction (stretch ratio in the width direction / stretch ratio in the length direction) is preferably 1.2 or more and 1.7 or less, more preferably 1.2 or more and 1.6 or less.

[0241] For example, in the longitudinal direction, the stretch ratio is calculated as the ratio of the membrane conveying speed before stretching to the membrane conveying speed after stretching. In the width direction, the stretch ratio is calculated as the ratio of the membrane width before stretching to the membrane width after stretching.

[0242] There are no particular limitations on the melting point (Tm) of the first temperature scan of this polyester film. From the viewpoint of practical heat resistance, it is preferably 230°C or higher, more preferably 235°C or higher, and more preferably 240°C or higher. Furthermore, the melting point (Tm) of the first temperature scan of this polyester film is preferably 250°C or lower, more preferably 248°C or lower. The preferred range for the melting point (Tm) of the first temperature scan of this polyester film is 235–250°C, more preferably 240–248°C.

[0243] Furthermore, the melting point (Tm) of the second temperature scan of this polyester film is not particularly limited, but from the viewpoint of heat resistance, it is, for example, 223°C or higher, preferably 228°C or higher, and more preferably 233°C or higher. Furthermore, the melting point (Tm) of the second temperature scan of this polyester film is preferably 247°C or lower, more preferably 245°C or lower. The preferred range for the melting point (Tm) of the second temperature scan of this polyester film is 228–245°C, more preferably 233–243°C.

[0244] It should be noted that the melting point (Tm) was determined according to JIS K7121 (2012) using a differential scanning calorimeter (DSC) under conditions of -70 to 280°C, a heating rate of 10°C / min, a holding time of 10 minutes, and a cooling rate of 600°C / min. The value of the peak tip (melting peak temperature) observed during the first heating was taken as the melting point of the first heating scan, and the value of the peak tip (melting peak temperature) of the second heating (during the reheating) was taken as the melting point of the second heating scan.

[0245] Furthermore, the polyester film preferably exhibits a single melting peak during the heating of the first and / or second heating scans (at least one of the first and second heating scans) obtained using differential scanning calorimetry, and more preferably, a single melting peak during both the first and second heating scans. If there is only one melting peak, the polyester film is less prone to softening at low temperatures. Therefore, when used as an outer casing material for energy storage devices, it is easier to prevent deterioration of the outer casing material even if the battery releases heat and heats it. Furthermore, it has the advantage of being able to stably produce a film even when the heat-setting temperature is increased in the manufacturing method described later. It should be noted that, for the polyester film, this can be adjusted so that the melting peak is singular by making PBT and PET miscible.

[0246] It should be noted that the statement "the melting peak obtained by differential scanning calorimetry during heating is one" refers to the measurement, according to JIS K7121 (2012), using a differential scanning calorimeter (DSC) under conditions of -70 to 280°C, a heating rate of 10°C / min, a holding time of 10 minutes, and a cooling rate of 600°C / min, and the number of melting peaks observed upon reheating is one. For the melting peak of the first heating scan, its peak tip is preferably observed in the range of 230 to 250°C, more preferably in the range of 235 to 248°C, and even more preferably in the range of 240 to 248°C. For the melting peak of the second heating scan, its peak tip is preferably observed in the range of 223 to 247°C, more preferably in the range of 228 to 245°C, and even more preferably in the range of 233 to 243°C.

[0247] There are no particular limitations on the glass transition temperature (Tg) of this polyester film, but it is, for example, 60°C or higher, preferably 61°C or higher, and more preferably 62°C or higher. Furthermore, the glass transition temperature (Tg) of this polyester film is preferably 72°C or lower, and more preferably 70°C or lower. The preferred range for the glass transition temperature (Tg) of this polyester film is 61–72°C, and more preferably 62–70°C. It should be noted that the glass transition temperature (Tg) is determined according to JIS K7121 (2012) 3.(3) using a differential scanning calorimeter (DSC) under conditions of -70–280°C, a heating rate of 10°C / min, a holding time of 10 minutes, and a cooling rate of 600°C / min, using the midpoint glass transition temperature during the reheating process.

[0248] [Manufacturing method of this polyester film]

[0249] As a method for manufacturing polyester film, a known film-forming method can be appropriately employed. For example, a film-forming raw material containing polyester and other raw materials can be melted, sheeted, and stretched for purposes such as improving strength to produce the desired polyester film. Without particular limitations, from the viewpoint of controlling the tensile yield stress, tensile elongation at break, tensile stress at break, and various characteristics of the stress-strain curve of this polyester film within the aforementioned preferred ranges, the following manufacturing conditions are preferred.

[0250] For example, in the successive biaxial stretching process, in the step of using an extruder to melt-extrude a film-forming raw material containing polyester and other materials from a die and then cooling and solidifying the molten sheet using a cooling roller to obtain an unstretched sheet, the extrusion temperature during melt extrusion from the die is preferably 270°C or higher, more preferably 275°C or higher, even more preferably 280°C or higher, and preferably 300°C or lower, more preferably 295°C or lower, even more preferably 290°C or lower. The preferred range for the extrusion temperature during melt extrusion from the die is preferably 270–300°C, more preferably 275–295°C, and even more preferably 280°C–290°C.

[0251] Furthermore, the temperature of the cooling roller is preferably 10°C or higher, more preferably 15°C or higher, and even more preferably 20°C or higher. It is also preferably 40°C or lower, more preferably 35°C or lower, and even more preferably 30°C or lower. The preferred temperature range for the cooling roller is 10–40°C, more preferably 15–35°C, and even more preferably 20–30°C.

[0252] It should be noted that, in order to improve the flatness of the sheet, it is preferable to improve the tightness between the sheet and the rotating cooling drum. Electrostatic application and liquid coating methods can be appropriately adopted.

[0253] Furthermore, the temperature conditions in the stretching process, specifically the stretching process along the longitudinal dimension (MD) (longitudinal stretching process), are preferably 60°C or higher, more preferably 62°C or higher, and even more preferably 64°C or higher. Additionally, they are preferably 75°C or lower, more preferably 74°C or lower, and even more preferably 73°C or lower. The preferred range for the temperature conditions in the stretching process along the longitudinal dimension (MD) (longitudinal stretching process) is 60–75°C, more preferably 62–74°C, and even more preferably 64–73°C.

[0254] Furthermore, the stretching ratio in the longitudinal stretching process (MD) is preferably 3 times or more, more preferably 3.3 times or more, and even more preferably 3.4 times or more. It is also preferably 4.2 times or less, more preferably 4 times or less, and even more preferably 3.8 times or less. The preferred range for the stretching ratio in the longitudinal stretching process (MD) is 3 to 4.2 times, more preferably 3.3 to 4 times, and even more preferably 3.4 to 3.8 times.

[0255] Furthermore, the temperature conditions in the secondary stretching process, namely the stretching process in the width direction (TD) (transverse stretching process), are preferably 70°C or higher, more preferably 80°C or higher, and even more preferably 85°C or higher. Furthermore, they are preferably 120°C or lower, more preferably 110°C or lower, and even more preferably 105°C or lower. The preferred range for the temperature conditions in the width direction (TD) stretching process (transverse stretching process) is 70–120°C, more preferably 80–110°C, and even more preferably 85–105°C.

[0256] Furthermore, the stretching ratio in the width direction (TD) stretching process (transverse stretching process) is preferably 3.5 times or more, more preferably 3.8 times or more, and even more preferably 4 times or more. It is also preferably 6 times or less, more preferably 5.5 times or less, and even more preferably 5.2 times or less. The preferred range for the stretching ratio in the width direction (TD) stretching process (transverse stretching process) is 3.5 to 6 times, more preferably 3.8 to 5.5 times, and even more preferably 4 to 5.2 times.

[0257] Furthermore, the preheating temperature conditions after the first stretching process and before the second stretching process are preferably 65°C or higher, more preferably 70°C or higher, and even more preferably 75°C or higher. Additionally, they are preferably 110°C or lower, more preferably 105°C or lower, and even more preferably 100°C or lower. The preferred range for the preheating temperature conditions is 65–110°C, more preferably 70–105°C, and even more preferably 75–100°C.

[0258] The preheating time is preferably about 1 to 12 seconds, more preferably about 2 to 11 seconds, and even more preferably about 3 to 10 seconds.

[0259] Furthermore, after the secondary stretching process, the heat-setting temperature conditions in the heat-setting treatment process, which is performed under tension or relaxation of 10% or less, preferably 7%, are preferably 180°C or higher, more preferably 190°C or higher, even more preferably 195°C or higher, and particularly preferably 200°C or higher. Additionally, they are preferably 240°C or lower, more preferably 230°C or lower, even more preferably 225°C or lower, and particularly preferably 220°C or lower. The preferred range for the heat-setting temperature conditions is preferably 180–240°C, more preferably 190–230°C, even more preferably 195–225°C, and particularly preferably 200–220°C.

[0260] The heat setting time is preferably about 3 to 15 seconds, more preferably about 4 to 14 seconds, and even more preferably about 5 to 13 seconds.

[0261] Alternatively, after the heat setting process, a cooling treatment can be performed in a cooling zone at a relaxation level of 0–20%, 0.5–15%, preferably 1–10%, and more preferably 1.5–7%. The cooling temperature is preferably 120–160°C, and more preferably 130°C–150°C.

[0262] It should be noted that by setting the preheating temperature, stretching temperature, and stretching ratio to slightly lower than usual and the heat setting temperature to slightly higher than usual, it is easy to control the tensile yield stress, tensile elongation at break, tensile fracture stress, and stress-strain curve characteristics within preferred ranges. Furthermore, by controlling these parameters as described above, localized stress concentration during molding is suppressed, and stress homogenization is promoted, thus achieving excellent formability while maintaining excellent heat resistance to withstand heat welding. This balance of excellent formability and heat resistance becomes even more pronounced when laminated with polyamide layers.

[0263] <First adhesive layer 2>

[0264] The first adhesive layer 2 is a layer that may be arbitrarily included in this outer material. It is a layer provided between the polyester film constituting the substrate layer 1 and the layer adjacent to its inner layer side. For example, it is a layer provided between the polyester film constituting the substrate layer 1 and the polyamide film constituting the polyamide layer 3, or a layer provided between the polyester film constituting the substrate layer 1 and the barrier layer 5.

[0265] The adhesive used in the first adhesive layer 2 can be any adhesive capable of bonding the polyester film to a layer adjacent to its inner layer, such as the polyamide film constituting the polyamide layer 3, without particular limitation. It can be any type of adhesive, such as chemically reactive, solvent-volatile, heat-melting, or hot-pressing adhesive. Furthermore, it can be a two-component curing adhesive, a one-component curing adhesive, or a resin that does not undergo a curing reaction.

[0266] There are no particular limitations on the adhesive components contained in the adhesive, and examples include polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyethylene isophthalate, and copolyesters; polyethers; polyurethanes; epoxy resins; phenolic resins; polyamides such as nylon 6, nylon 66, and nylon 12; polyolefin resins such as polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins; polyvinyl acetate; cellulose; (meth)acrylic resins; polyimides; polycarbonates; amino resins such as urea-formaldehyde resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; and silicone resins. They can be used alone, or in combination of two or more. Among these, polyurethane adhesives are preferred.

[0267] Furthermore, these adhesive components can also be used in conjunction with a curing agent to improve bond strength. Examples of such curing agents include polyisocyanates, polyfunctional epoxy resins, oxazoline-containing polymers, polyamine resins, and acid anhydrides. They can be used alone or in combination of two or more.

[0268] Examples of polyurethane adhesives include those comprising a base agent containing a polyol compound and a curing agent containing an isocyanate compound. For instance, two-component curing polyurethane adhesives using polyols such as polyester polyols, polyether polyols, and acrylic polyols as the base agent and aromatic or aliphatic polyisocyanates as the curing agent are preferred.

[0269] Furthermore, as a polyol compound, polyester polyols that have hydroxyl groups in the side chains in addition to the terminal hydroxyl groups of the repeating units are preferred.

[0270] Furthermore, the first adhesive layer 2 may also contain colorants, thermoplastic elastomers, tackifiers, fillers, etc., as long as it does not impede adhesion. As colorants, known colorants such as pigments and dyes can be used. They can be used alone, or in combination of two or more.

[0271] Examples of pigments include organic pigments such as azo, phthalocyanine, quinacridone, anthraquinone, dioxazine, indigo thiocyanate, perylene ketone-perylene, isopycindo, and benzimidazolone pigments; inorganic pigments such as carbon black, titanium dioxide, cadmium, lead, chromium oxide, and iron pigments; and mica powder and fish scale foil. These can be used individually or in combination of two or more.

[0272] There are no particular limitations on the average particle size of the pigment, for example, it is about 0.05 to 5 μm, preferably about 0.08 to 2 μm. It should be noted that the average particle size of the pigment is set as the median particle size measured using a laser diffraction / scattering particle size distribution measuring device.

[0273] The amount of pigment in the first adhesive layer 2 is not particularly limited as long as the outer packaging material will be colored. For example, it is about 5 to 60% by mass, preferably about 10 to 40% by mass.

[0274] The first adhesive layer 2 can be composed of a single layer or a laminate of two or more layers. There is no particular limitation on the thickness (total thickness) of the first adhesive layer 2, for example, it can be about 1 to 10 μm or about 1 to 5 μm.

[0275] <Polyamide layer 3>

[0276] The polyamide layer 3 is a layer that can be arbitrarily included in this outer casing material. It is a layer designed to provide excellent formability and is laminated onto the substrate layer 1. The polyamide layer 3 can be arbitrarily laminated onto the substrate layer 1 via the first adhesive layer 2. There are no particular limitations on the polyamide used to form the polyamide layer 3. From the viewpoint of balancing the moldability and heat resistance of this outer material, examples include: aliphatic polyamides such as copolymers of nylon 12, nylon 46, nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, nylon 6I6T (I represents isophthalic acid, T represents terephthalic acid) and polyadipamide-isophthalic acid (MXD6) containing structural units derived from terephthalic acid and / or isophthalic acid; alicyclic polyamides such as polyaminomethylcyclohexyl adipamide (PACM6); polyamides further copolymerized with lactam components, isocyanate components such as 4,4'-diphenylmethane-diisocyanate, polyesteramide copolymers as copolymers of copolyamides with polyesters and polyalkylene ether diols, polyether esteramide copolymers; and copolymers thereof. They can be used individually, or in combination of two or more.

[0277] From the viewpoint of balancing the formability and heat resistance of the outer casing material, the polyamide layer 3 is preferably composed of a stretched film, and more preferably of a biaxially stretched polyamide film, particularly a biaxially stretched nylon film. The stretched polyamide film can be manufactured using conventionally known methods. For example, methods for forming a biaxially stretched polyamide film include sequential biaxial stretching, blown film blowing, and simultaneous biaxial stretching, with sequential biaxial stretching being preferred.

[0278] The polyamide layer 3 can be composed of a single layer or a laminate of two or more layers. The thickness (total thickness) of the polyamide layer 3 is not particularly limited, but from the viewpoint of achieving excellent formability, it is preferably about 30 μm or less, more preferably about 28 μm or less, and even more preferably about 25 μm or less. Furthermore, it is about 1 μm or more, more preferably about 5 μm or more, and even more preferably about 10 μm or more. The preferred range for the thickness (total thickness) of the polyamide layer 3 is about 1 to 30 μm, more preferably about 5 to 28 μm, and even more preferably about 10 to 25 μm.

[0279] It should be noted that, from the viewpoint of further improving formability, the thickness ratio of substrate layer 1 to polyamide layer 3 (substrate layer 1: polyamide layer 3) is preferably in the range of about 2:1 to 1:5, more preferably in the range of about 1.5:1 to 1:4, and even more preferably in the range of about 1:1 to 1:3.

[0280] <Second adhesive layer 4>

[0281] The second adhesive layer 4 is a layer that may be arbitrarily included in this outer material. It is a layer provided between the polyamide film constituting the polyamide layer 3 and the metal foil constituting the barrier layer 5 (described later). The second adhesive layer 4 is the same as the one described in the "first adhesive layer 2" section. For example, the adhesive used in the second adhesive layer 4 is not particularly limited as long as it can bond the polyamide film constituting the polyamide layer 3 to the metal foil constituting the barrier layer 5. It can be appropriately selected from the adhesives exemplified in the first adhesive layer 2.

[0282] The second adhesive layer 4 can be composed of a single layer or a laminate of two or more layers. The thickness (total thickness) of the second adhesive layer 4 is not particularly limited, for example, it can be about 1 to 10 μm, about 1.5 to 5 μm, or about 2 to 4 μm.

[0283] <Barrier Layer 5>

[0284] The barrier layer 5 is a layer that prevents water vapor, oxygen, light, etc., from entering the battery. The barrier layer 5 is preferably a metal layer, that is, a layer formed of metal.

[0285] Examples of metals constituting barrier layer 5 include aluminum, stainless steel, and titanium. Among these, aluminum is preferred.

[0286] The barrier layer 5 can be composed of, for example, metal foil, metal vapor-deposited film, inorganic oxide vapor-deposited film, carbon-containing inorganic oxide vapor-deposited film, or film having such vapor-deposited films. Among these, it is preferably composed of metal foil, and more preferably of aluminum alloy foil or stainless steel foil. Furthermore, from the viewpoint of preventing wrinkles and pinholes in the barrier layer 5 during the manufacture of this outer packaging material, the barrier layer 5 is more preferably composed of, for example, annealed aluminum (JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, JIS H4000:2014 A8079P-O) or other soft aluminum alloy foil.

[0287] The barrier layer 5 can be composed of a single layer or a laminate of two or more layers. The thickness (total thickness) of the barrier layer 5 is not particularly limited as long as it functions to block water vapor, etc. For example, it is about 10 μm or more, preferably about 20 μm or more, more preferably about 30 μm or more, even more preferably about 35 μm or more, about 40 μm or more, about 45 μm or more, or about 55 μm or more. In addition, it is preferably about 200 μm or less, more preferably about 150 μm or less, even more preferably about 100 μm or less, and even more preferably about 85 μm or less. As preferred ranges, it is about 10 to 200 μm, about 20 to 150 μm, about 30 to 100 μm, about 35 to 85 μm, or about 45 to 85 μm.

[0288] Furthermore, from the viewpoints of stabilizing the adhesion and preventing dissolution and corrosion, it is preferable that at least one side, preferably both sides, of the barrier layer 5 undergo a chemical formation treatment. Here, chemical formation treatment refers to the treatment of forming an acid-resistant film on the surface of the barrier layer 5. The barrier layer 5 may have an acid-resistant film on one side, on both sides, or without an acid-resistant film.

[0289] Examples of chemical formation treatments include chromate treatment using chromium compounds such as chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium dihydrogen phosphate, acetoacetate chromate, chromium chloride, and potassium chromium sulfate; phosphoric acid treatment using phosphoric acid compounds such as sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphoric acid; and chromate treatment using an aminophenol polymer having repeating units shown in the following general formulas (1) to (4). It should be noted that in the aminophenol polymer, the repeating units shown in the following general formulas (1) to (4) may be a single type or an arbitrary combination of two or more.

[0290] [Chemical Formula 1]

[0291]

[0292] [Chemical Formula 2]

[0293]

[0294] [Chemical Formula 3]

[0295]

[0296] [Chemical Formula 4]

[0297]

[0298] In general formulas (1) to (4), X represents a hydrogen atom, hydroxyl group, alkyl group, hydroxyalkyl group, allyl group, or benzyl group. Furthermore, R... 1 and R 2 Each may be the same or different, representing hydroxyl, alkyl, or hydroxyalkyl. In general formulas (1) to (4), X and R are used as X and R respectively. 1 and R 2 The alkyl groups shown can be, for example, straight-chain or branched alkyl groups with 1 to 4 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and tert-butyl. Furthermore, as X and R... 1 and R 2The hydroxyalkyl groups shown include, for example, hydroxymethyl, 1-hydroxyethyl, 2-hydroxyethyl, 1-hydroxypropyl, 2-hydroxypropyl, 3-hydroxypropyl, 1-hydroxybutyl, 2-hydroxybutyl, 3-hydroxybutyl, 4-hydroxybutyl, etc., which are straight-chain or branched alkyl groups with 1 to 4 carbon atoms and one hydroxyl substituted. In general formulas (1) to (4), X, R 1 and R 2 The alkyl and hydroxyalkyl groups shown may be the same or different. In general formulas (1) to (4), X is preferably a hydrogen atom, a hydroxyl group or a hydroxyalkyl group. The number average molecular weight of the aminophenol polymer having the repeating units shown in general formulas (1) to (4) is preferably 5 million to 1 million, more preferably 10 million to 20,000.

[0299] Furthermore, as a chemical treatment method to impart corrosion resistance to the barrier layer 5, the following methods can be listed: A substance containing metal oxides such as alumina, titanium oxide, cerium oxide, and tin oxide, and barium sulfate particles dispersed in phosphoric acid is coated, and sintered at 150°C or higher, thereby forming an acid-resistant film on the surface of the barrier layer 5. Furthermore, a resin layer formed by crosslinking a cationic polymer using a crosslinking agent can be further formed on the acid-resistant film. Examples of cationic polymers include polyethyleneimine, ionic polymeric complexes formed from polyethyleneimine and polymers containing carboxylic acids, primary amine-grafted acrylic resins formed by grafting a primary amine onto an acrylic acid backbone, polyallylamine or its derivatives, and aminophenol. Only one of these can be used, or two or more can be used in combination. Furthermore, examples of crosslinking agents include compounds having at least one functional group selected from the group consisting of isocyanate groups, glycidyl groups, carboxyl groups, and oxazoline groups, and silane coupling agents. Only one of these can be used, or two or more can be used in combination.

[0300] Furthermore, as a specific method for setting an acid-resistant film, for example, firstly, the inner layer side of at least the aluminum alloy foil is degreased using a known treatment method such as alkaline impregnation, electrolytic cleaning, acid cleaning, electrolytic acid cleaning, or acid activation. Then, a treatment solution (aqueous solution) mainly composed of metal phosphate salts such as chromium phosphate, titanium phosphate, zirconium phosphate, and zinc phosphate, or a mixture thereof, or a treatment solution (aqueous solution) mainly composed of non-metal phosphate salts and a mixture thereof, or a mixture thereof with aqueous synthetic resins such as acrylic resins, phenolic resins, or urethane resins, is applied to the degreased surface by a known coating method such as roller coating, gravure printing, or impregnation. This forms an acid-resistant film. For example, when treated with a chromium phosphate-based treatment solution, an acid-resistant film is formed from chromium phosphate, aluminum phosphate, alumina, aluminum hydroxide, aluminum fluoride, etc.; when treated with a zinc phosphate-based treatment solution, an acid-resistant film is formed from zinc phosphate hydrate, aluminum phosphate, alumina, aluminum hydroxide, aluminum fluoride, etc.

[0301] In addition, as other examples of specific methods for setting an acid-resistant coating, for example, firstly, at least the inner layer side of the aluminum alloy foil is degreased using well-known treatment methods such as alkaline immersion, electrolytic cleaning, acid cleaning, electrolytic acid cleaning, and acid activation, and then the degreased surface is subjected to well-known anodizing treatment, thereby forming an acid-resistant coating.

[0302] Furthermore, as another example of acid-resistant coatings, phosphate-based and chromate-based coatings can be listed. Examples of phosphate-based coatings include zinc phosphate, iron phosphate, manganese phosphate, calcium phosphate, and chromium phosphate, while examples of chromate-based coatings include chromium chromate.

[0303] Furthermore, as another example of acid-resistant coatings, the formation of acid-resistant coatings from phosphates, chromates, fluorides, triazine thiols, etc., exhibits the following effects: preventing delamination between aluminum and the layer that functions as a substrate during embossing; preventing the dissolution and corrosion of the aluminum surface due to hydrogen fluoride generated by the reaction of electrolytes and moisture, especially the dissolution and corrosion of alumina present on the aluminum surface; and improving the adhesion (wetting) of the aluminum surface, preventing delamination between the layer that functions as a substrate and the aluminum during hot welding; and preventing delamination between the layer that functions as a substrate and the aluminum during pressure forming in embossing. Among the substances forming the acid-resistant coating, applying an aqueous solution composed of phenolic resin, chromium (III) fluoride compound, and phosphoric acid to the aluminum surface, followed by drying and sintering, is a good method.

[0304] Alternatively, the acid-resistant film may comprise a layer having cerium oxide, phosphoric acid or phosphate, an anionic polymer, and a crosslinking agent for crosslinking the anionic polymer, wherein 1 to 100 parts by weight of the phosphoric acid or phosphate are added relative to 100 parts by weight of the cerium oxide. Preferably, the acid-resistant film further comprises a multilayer structure having a layer having a cationic polymer and a crosslinking agent for crosslinking the cationic polymer.

[0305] Furthermore, the anionic polymer is preferably poly(meth)acrylic acid or a salt thereof, or a copolymer with (meth)acrylic acid or a salt thereof as the main component. In addition, the crosslinking agent is preferably at least one selected from the group consisting of compounds having any one of the functional groups of isocyanate group, glycidyl group, carboxyl group, and oxazoline group, and silane coupling agents.

[0306] Furthermore, the phosphoric acid or phosphate is preferably condensed phosphoric acid or condensed phosphate.

[0307] The formation treatment can be performed using only one formation treatment or by combining two or more formation treatments. Furthermore, these formation treatments can be performed using only one compound, or by combining two or more compounds. Among the formation treatments, chromate treatments and formation treatments combining chromium compounds, phosphoric acid compounds, and aminophenol polymers are preferred. Among the chromium compounds, chromate compounds are preferred.

[0308] Specific examples of acid-resistant films include those containing at least one of phosphates, chromates, fluorides, and triazine thiols. Furthermore, acid-resistant films containing cerium compounds are also preferred. Cerium oxide is preferred as the cerium compound.

[0309] Furthermore, specific examples of acid-resistant coatings include phosphate-based coatings, chromate-based coatings, fluoride-based coatings, and triazine thiol compound coatings. An acid-resistant coating can be one of these or a combination of several. Moreover, an acid-resistant coating can be formed after degreasing the chemically treated surface of the aluminum alloy foil using a treatment solution formed from a mixture of metal phosphates and aqueous synthetic resins, or a treatment solution formed from a mixture of non-metal phosphates and aqueous synthetic resins.

[0310] It should be noted that the composition of acid-resistant films can be analyzed, for example, using time-of-flight secondary ion mass spectrometry (TOF-MS). By analyzing the composition of acid-resistant films using TOF-MS, for example, detecting substances originating from Ce... + and Cr + At least one of the peaks.

[0311] Preferably, the surface of the aluminum alloy foil has an acid-resistant film containing at least one element selected from the group consisting of phosphorus, chromium, and cerium. It should be noted that X-ray photoelectron spectroscopy can be used to confirm that the acid-resistant film on the surface of the aluminum alloy foil of the battery packaging material contains at least one element selected from the group consisting of phosphorus, chromium, and cerium. Specifically, firstly, the heat-welding resin layer 6 and the second adhesive layer 4 laminated on the aluminum alloy foil are physically peeled off. Next, the aluminum alloy foil is placed in an electric furnace and heated to approximately 300°C for approximately 30 minutes to remove organic components present on the surface of the aluminum alloy foil. Then, X-ray photoelectron spectroscopy of the surface of the aluminum alloy foil is used to confirm the presence of these elements.

[0312] There is no particular limitation on the amount of acid-resistant film formed on the surface of barrier layer 5 during the chemical formation process. For example, if the chromate treatment described above is being performed, it is desirable that every 1m of the surface of barrier layer 5 has an acid-resistant film. 2 It contains a chromium compound in a proportion of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, converted from chromium; a phosphorus compound in a proportion of about 0.5 to 50 mg, preferably about 1 to 40 mg, converted from phosphorus; and an amino-modified phenol polymer in a proportion of about 1 to 200 mg, preferably about 5 to 150 mg.

[0313] There are no particular limitations on the thickness of the acid-resistant film. However, considering the film's cohesiveness and its adhesion to the barrier layer 5 and the heat-fused resin layer, it is preferably about 1 nm to 10 μm, more preferably about 1 to 100 nm, and even more preferably about 1 to 50 nm. It should be noted that the thickness of the acid-resistant film can be determined by observation using a transmission electron microscope, or by a combination of observation using a transmission electron microscope and energy-dispersive X-ray spectroscopy or electron beam energy loss spectroscopy.

[0314] The formation treatment is performed as follows: a solution containing a compound for forming an acid-resistant film is applied to the surface of the barrier layer 5 using methods such as bar coating, roller coating, gravure coating, or immersion coating, followed by heating the barrier layer 5 to a temperature of approximately 70–200°C. Alternatively, before performing the formation treatment on the barrier layer 5, it can be pre-treated by degreasing using methods such as alkaline immersion, electrolytic cleaning, acid cleaning, or electrolytic acid cleaning. By performing degreasing treatment in this way, the surface formation treatment of the barrier layer 5 can be performed more effectively.

[0315] <Thermo-Melt Resin Layer 6>

[0316] The heat-fusion resin layer 6 is the innermost layer, which is the layer that seals the battery components by heat-fusion bonding the heat-fusion resin layers 6 to each other during battery assembly.

[0317] The resin component used in the heat-melting resin layer 6 can be heat-melted without any particular limitation. Examples include polyolefins, cyclic polyolefins, carboxylic acid-modified polyolefins, and carboxylic acid-modified cyclic polyolefins. That is, the resin constituting the heat-melting resin layer 6 may or may not contain a polyolefin backbone, but it is preferable to contain a polyolefin backbone.

[0318] It should be noted that the resin constituting the heat-fusion resin layer 6 contains a polyolefin skeleton, which can be analyzed by methods such as infrared spectroscopy and gas chromatography-mass spectrometry; there are no particular limitations on the analytical methods. For example, when using infrared spectroscopy to determine maleic anhydride-modified polyolefins, at a wavenumber of 1760 cm⁻¹... -1 Nearby and wave number 1780cm -1 A peak originating from maleic anhydride was detected nearby. However, if the acid modification degree is low, the peak may sometimes become too small to be detected. In such cases, analysis can be performed using nuclear magnetic resonance spectroscopy.

[0319] Specifically, examples of the polyolefins include: low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, and other polyethylenes; homopolymer polypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene), and terpolymers of ethylene-butene-propylene. Among these, polyethylene and polypropylene are preferred, and polypropylene is particularly preferred.

[0320] The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer. Examples of olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, butadiene, and isoprene. Furthermore, examples of cyclic monomers constituting the cyclic polyolefin include norbornene and other cyclic olefins; specifically, examples include cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornene and other cyclic dienes. Cyclic olefins are preferred, and norbornene is more preferred. Styrene may also be used as a constitutive monomer.

[0321] The carboxylic acid-modified polyolefin refers to a polymer modified by block polymerization or graft polymerization of the polyolefin with a carboxylic acid. Examples of carboxylic acids used in the modification include maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride.

[0322] The carboxylic acid-modified cyclic polyolefin refers to a polymer obtained by copolymerizing a portion of the monomers constituting the cyclic polyolefin with α,β-unsaturated carboxylic acids or their anhydrides, or by block polymerization or graft polymerization of α,β-unsaturated carboxylic acids or their anhydrides onto the cyclic polyolefin. The same applies to cyclic polyolefins modified with carboxylic acids. Furthermore, the carboxylic acid used in the modification is the same as that used in the modification of the acid-modified polyolefin.

[0323] Among these resin components, carboxylic acid-modified polyolefins are preferred, and carboxylic acid-modified polypropylenes are even more preferred.

[0324] Lubricant may also be included in the heat-melting resin layer 6. Furthermore, the lubricant present on the surface of the heat-melting resin layer 6 may be formed by the exudation of lubricant contained in the resin constituting the heat-melting resin layer 6, or it may be formed by coating the surface of the heat-melting resin layer 6 with lubricant. When the heat-melting resin layer 6 contains lubricant, the moldability of this outer material can be improved. There are no particular limitations on the lubricant; known lubricants can be used, such as those exemplified for the described polyester film. They can be used alone, or in combination of two or more.

[0325] The amount of lubricant present on the surface of the heat-melting resin layer 6 is not particularly limited, but from the viewpoint of improving the formability of this outer casing material, it is preferably 10 to 50 mg / m³. 2 Approximately, more preferably 15–40 mg / m² 2 about.

[0326] The heat-melting resin layer 6 can be formed from a single resin component, or it can be formed from a blend of two or more resin components. Furthermore, the heat-melting resin layer 6 can be a single layer or a laminate of two or more layers. Additionally, the heat-melting resin layer 6 can also be composed of either a stretched film or an unstretched film.

[0327] Furthermore, the thickness (total thickness) of the heat-fusion resin layer 6 is approximately 15 to 100 μm, more preferably approximately 15 to 40 μm, from the viewpoint of making the battery packaging material as thin as possible and suppressing curling after molding.

[0328] It should be noted that, in order to improve the adhesion between the barrier layer 5 and the thermoplastic resin layer 6, this outer material may also provide an adhesive layer (hereinafter sometimes referred to as "third adhesive layer") between the barrier layer 5 and the thermoplastic resin layer 6 as needed.

[0329] The third adhesive layer is the same as the one described in the "First Adhesive Layer 2" column. For example, the adhesive used in the third adhesive layer between the barrier layer 5 and the thermosetting resin layer 6 is not particularly limited as long as it can bond the metal foil constituting the barrier layer 5 to the resin film constituting the thermosetting resin layer. It can be appropriately selected from the adhesives exemplified in "First Adhesive Layer 2".

[0330] From the viewpoint of firmly bonding the third adhesive layer to the heat-melting resin layer 6, the resin used in forming the third adhesive layer preferably contains a polyolefin backbone, such as the polyolefins and acid-modified polyolefins exemplified in the aforementioned heat-melting resin layer 6. Furthermore, from the viewpoint of firmly bonding the barrier layer 5 to the third adhesive layer, the third adhesive layer preferably contains an acid-modified polyolefin. Examples of acid-modifying components include dicarboxylic acids such as maleic acid, itaconic acid, succinic acid, and adipic acid, their anhydrides, acrylic acid, and methacrylic acid. Among these, maleic anhydride is preferred from the perspectives of ease of modification and versatility. Furthermore, from the viewpoint of the heat resistance of the casing material for energy storage devices, the olefin component is preferably a polypropylene-based resin, and the third adhesive layer most preferably contains maleic anhydride-modified polypropylene.

[0331] As the resin used in forming the third adhesive layer, if it contains a polyolefin backbone, the third adhesive layer preferably contains a resin containing a polyolefin backbone as the main component, more preferably contains an acid-modified polyolefin as the main component, and even more preferably contains an acid-modified polypropylene as the main component.

[0332] The resin constituting the third adhesive layer contains a polyolefin skeleton, which can be analyzed, for example, by infrared spectroscopy, gas chromatography-mass spectrometry, etc., and the analytical method is not particularly limited. Furthermore, the resin constituting the adhesive layer may contain acid-modified polyolefins, which can be analyzed, for example, by measuring maleic anhydride-modified polyolefins using infrared spectroscopy at a wavenumber of 1760 cm⁻¹. -1 Nearby and wave number 1780cm -1 A peak originating from maleic anhydride was detected nearby. However, if the acid modification degree is low, the peak may sometimes become too small to be detected. In such cases, analysis can be performed using nuclear magnetic resonance spectroscopy.

[0333] When manufacturing this exterior material by laminating the third adhesive layer with the barrier layer 5, the heat-melting resin layer 6, etc., a pre-formed resin film can be used as the third adhesive layer. Alternatively, the heat-melting resin forming the third adhesive layer can be formed on the surface of the barrier layer 5, the heat-melting resin layer 6, etc., by extrusion molding, coating, etc., to form a third adhesive layer formed of resin film.

[0334] The thickness (total thickness) of the third adhesive layer is not particularly limited, but is preferably about 50 μm or less, about 40 μm or less, or about 30 μm or less. Furthermore, the thickness (total thickness) of the adhesive layer is preferably about 1 μm or more, about 5 μm or more, or about 10 μm or more. Moreover, the range of the thickness (total thickness) of the third adhesive layer is preferably about 1–50 μm, about 5–40 μm, or about 10–30 μm.

[0335] Furthermore, when using the resin exemplified in the thermoplastic resin layer 6, the third adhesive layer can be formed, for example, by extrusion molding of the thermoplastic resin layer 6 and the third adhesive layer. Moreover, in the case where the thermoplastic resin layer 6 and the third adhesive layer are formed by co-extrusion molding, the total thickness of the thermoplastic resin layer 6 and the third adhesive layer has a lower limit of approximately 35 μm, approximately 55 μm, and approximately 75 μm, and an upper limit of approximately 45 μm, approximately 65 μm, and approximately 85 μm, with a numerical range of approximately 35–45 μm, approximately 35–65 μm, approximately 35–85 μm, approximately 55–65 μm, approximately 55–85 μm, and approximately 75–85 μm.

[0336] Furthermore, this outer material may also have a coloring layer between the substrate layer 1 and the first adhesive layer 2, and between the first adhesive layer 2 and the polyamide layer 3. The coloring layer can be formed, for example, by applying an ink containing a colorant to the surface of the layer to be applied. Known colorants such as pigments and dyes can be used as the colorant. Specific examples of the colorant are the same as those exemplified in the <First Adhesive Layer 2> section.

[0337] In addition, in order to improve or stabilize the film-forming properties, lamination processing, and adaptability of the final product to two processing steps, each layer constituting the laminate may also undergo surface activation treatments such as corona treatment, sandblasting treatment, oxidation treatment, and ozone treatment as needed.

[0338] <Application>

[0339] This outer packaging material is used in packaging for sealing and accommodating energy storage device components such as positive electrode, negative electrode, and electrolyte. That is, an energy storage device can be manufactured by accommodating energy storage device components having at least a positive electrode, a negative electrode, and an electrolyte in a packaging formed from this outer packaging material.

[0340] Specifically, using this outer casing material, a storage device element having at least a positive electrode, a negative electrode, and an electrolyte is covered in such a way that a flange portion (the area where the heat-melting resin layers contact each other) is formed at the periphery of the storage device element with the metal terminals respectively connected to the positive and negative electrodes protruding outwards. The heat-melting resin layers of the flange portion are then heat-sealed to seal it, thereby providing a storage device using the outer casing material for storage devices. It should be noted that when the storage device element is housed in a package formed from this outer casing material, the package is formed such that the heat-melting resin portion of this outer casing material is the inner side (the surface in contact with the storage device element).

[0341] This casing material is preferably used in energy storage devices such as batteries (including capacitors, condensers, and capacitors). Furthermore, this casing material can be used in either primary or secondary batteries, but is preferred for secondary batteries. There are no particular limitations on the types of secondary batteries to which this casing material can be used; examples include lithium-ion batteries, lithium-ion polymer batteries, all-solid-state batteries, semi-solid-state batteries, quasi-solid-state batteries, polymer batteries, all-resin batteries, lead-acid batteries, nickel-metal hydride batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, metal-air batteries, multivalent cation batteries, capacitors, and capacitors. Among these secondary batteries, lithium-ion batteries and lithium-ion polymer batteries are preferred applications for this casing material.

[0342] <Manufacturing Method of This Exterior Material>

[0343] Regarding the manufacturing method of this exterior material, it is not particularly limited as long as a laminate formed by stacking the aforementioned layers is used. For example, firstly, a laminate consisting of a substrate layer 1, a first adhesive layer 2, and a polyamide layer 3 stacked sequentially is formed (hereinafter, sometimes referred to as "laminate A"). Specifically, laminate A can be formed by the following dry lamination method: using a coating method such as gravure coating or roller coating, the adhesive used to form the first adhesive layer 2 is applied to the substrate layer 1 or the polyamide layer 3 and dried. Then, the polyamide layer 3 or the substrate layer 1 is laminated to cure the first adhesive layer 2.

[0344] Next, using laminate A, a laminate consisting of a substrate layer 1, a first adhesive layer 2, a polyamide layer 3, a second adhesive layer 4, and a barrier layer 5 is formed (hereinafter, sometimes also referred to as "laminate B"). Laminate B can be formed specifically by the following dry lamination method: using a coating method such as gravure coating or roller coating, the adhesive used to form the second adhesive layer 4 is applied to the polyamide layer 3 or the barrier layer 5, whose surface has been chemically treated as needed, and then dried. Afterward, the barrier layer 5 or the polyamide layer 3 is laminated to cure the second adhesive layer 4.

[0345] Furthermore, the formation sequence of laminate B is not limited to the above sequence, and can also be carried out by the following dry lamination method: using a gravure coating method, roller coating method or other coating method, the adhesive used to form the second adhesive layer 4 is applied to the polyamide layer 3 or the barrier layer 5 whose surface has been chemically treated as needed and then dried, and then the barrier layer 5 or the polyamide layer 3 is laminated to cure the second adhesive layer 4; then laminate B by the following dry lamination method: using a gravure coating method, roller coating method or other coating method, the adhesive used to form the first adhesive layer 2 is applied to the substrate layer 1 or the polyamide layer 3 and then dried, and then the polyamide layer 3 or the substrate layer 1 is laminated to cure the first adhesive layer 2.

[0346] Alternatively, for example, a laminate consisting of a substrate layer 1, a first adhesive layer 2, and a barrier layer 5 (hereinafter sometimes referred to as "laminate B'") can be formed instead of laminate B. Laminate B' can be formed specifically by a dry lamination method as follows: an adhesive for forming the first adhesive layer 2 is applied to the substrate layer 1 using a coating method such as gravure coating or roller coating, or a barrier layer 5 whose surface has undergone chemical formation treatment as needed, and then dried. The barrier layer 5 or the substrate layer 1 is then laminated, allowing the first adhesive layer 2 to cure.

[0347] Next, the heat-melting resin layer 6 is laminated onto the barrier layer 5 of laminate B or laminate B'. When the heat-melting resin layer 6 is directly laminated onto the barrier layer 5, it is sufficient to laminate the heat-melting resin layer 6 onto the barrier layer 5 of laminate B or laminate B' by means of hot lamination, extrusion lamination, or other methods.

[0348] Furthermore, when a third adhesive layer is provided between the barrier layer 5 and the thermoplastic resin layer 6, the following methods can be listed as examples: (1) a method of laminating by extruding the third adhesive layer and the thermoplastic resin layer 6 onto the barrier layer 5 of the laminate B or the laminate B' (co-extrusion lamination method, tandem lamination method); (2) a method of forming a laminate with the third adhesive layer and the thermoplastic resin layer 6 separately and laminating it onto the barrier layer 5 of the laminate B or the laminate B' by hot lamination; a method of forming a laminate with the third adhesive layer laminated onto the barrier layer 5 of the laminate B or the laminate B' and laminating it onto the barrier layer 5 of the laminate B or the laminate B' by hot lamination. (3) A method of laminating the heat-melting resin layer 6 with the heat-melting resin layer 6 by means of allowing the molten third adhesive layer to flow into the barrier layer 5 of the laminate B or the laminate B' and the heat-melting resin layer 6 pre-filmed into a sheet, and bonding the laminate B or the laminate B' to the heat-melting resin layer 6 via the third adhesive layer (sandwich lamination); (4) A method of applying an adhesive solution for forming the third adhesive layer to the barrier layer 5 of the laminate B or the laminate B' and drying it, and further laminating by means of sintering, etc., and laminating the heat-melting resin layer 6 pre-filmed into a sheet on the adhesive layer, etc.

[0349] As described above, for example, a laminate formed by sequentially forming a substrate layer 1, a first adhesive layer 2, a barrier layer 5, and a heat-melting resin layer 6, or a laminate formed by sequentially forming a substrate layer 1, a first adhesive layer 2, a polyamide layer 3, a second adhesive layer 4, a barrier layer 5, and a heat-melting resin layer 6, etc., may be further subjected to heat treatment to make the adhesion of the first adhesive layer 2 and the second adhesive layer 4 stronger, as needed.

[0350] Regarding the exterior materials, such as Figure 2 , Figure 3 As shown, in the outer material 100 formed by the laminate 10, the housing 100a for lithium-ion batteries, etc., is manufactured by cold forming using a molding die. The molding die is typically rectangular when viewed from above, and the housing 100a is also typically rectangular when viewed from above. The corners of the rectangular shape can be right angles, or they can be rounded instead of right angles.

[0351] Due to its excellent deep-drawing formability, this outer casing material has no particular limitations. For example, the ratio (d / S) of the area (S) to the recess depth (d) of the housing portion of a lithium-ion battery, etc., when viewed from above, can be set to 0.005 (mm / mm). 2 Above that, it can be further set to 0.006 (mm / mm) 2 The value above can also be set to 0.007–0.012 (mm / mm). 2 ).

[0352] It should be noted that, in the case of an approximate rectangle without corners and edges R, the distance between opposite sides of the molded article is measured separately for the long side and the short side, and the area is taken as the area (S).

[0353] In the case of an approximate rectangle with angular ridges R, the distance between the end of the ridge R on the side of the molded article and the corresponding opposite part is measured along the long side and the short side, and the product of these distances is taken as the area (S).

[0354] If the rectangle is not approximately rectangular, calculate the area of ​​the rectangle using the same method as for an approximately rectangular rectangle, and sum the results of combining the rectangles to obtain the area (S).

[0355] Specifically, for example, the area (S) of the housing 100a in the lithium-ion battery, etc., when viewed from above, is 1722.2 mm². 2 In the case of (31.6mm×54.5mm), the indentation depth (d) can be set to, for example, 8mm or more, 10mm or more, or 12 to 20mm.

[0356] It should be noted that there are no particular restrictions when manufacturing lithium-ion batteries or the like contained in this outer casing material. For example, if the housing portion 100a is rectangular when viewed from above, it is preferable that the long side of the rectangular portion when viewed from above corresponds to the MD of this polyester film, and the short side of the rectangular portion when viewed from above corresponds to the TD of this polyester film.

[0357] Example

[0358] The present invention will be further described in detail below with reference to embodiments, but the present invention is not limited to the following embodiments as long as it does not deviate from its spirit. It should be noted that in the examples, "parts" and "%" refer to mass standards.

[0359] First, the raw materials of the substrate layer used in the following embodiments and comparative examples are as follows.

[0360] <<Substrate Layer>>

[0361] <Polyethylene terephthalate, etc.>

[0362] •PET (1): Homopolymer polyethylene terephthalate, intrinsic viscosity 0.64 dL / g.

[0363] •PET(2): Homopolymer polyethylene terephthalate, intrinsic viscosity 0.85 dL / g.

[0364] PET MB(1): A masterbatch of polyethylene terephthalate matrix containing 0.55% by mass of silica spherical particles (average particle size 3.1 μm) with an intrinsic viscosity of 0.61 dL / g.

[0365] PET MB (2): A masterbatch of polyethylene terephthalate matrix containing 10% by mass of spherical organic particles (average particle size 4.1 μm) obtained by polymerizing acrylate monomers, styrene monomers and organosilicon monomers, with an intrinsic viscosity of 0.60 dL / g.

[0366] Polybutylene terephthalate (PET)

[0367] • PBT (1): Polybutylene terephthalate, manufactured by Mitsubishi Engineering-Plastics, NOVADURAN (registered trademark) 5008, intrinsic viscosity 0.85 dL / g.

[0368] • PBT (2): Polybutylene terephthalate, manufactured by Mitsubishi Engineering-Plastics, NOVADURAN (registered trademark) 5026, intrinsic viscosity 1.26 dL / g.

[0369] Biaxially stretched polyester films (PE1 to PE17) constituting the substrate layer are produced using the formulation and manufacturing conditions shown in Table 1 below. Specifically, as described below.

[0370] It should be noted that the PET / PBT (mass ratio) shown in Table 1 is the mass ratio of PET and PBT contained in the entire biaxially stretched polyester film with the following three-layer structure. Specifically, it is calculated in the form of the PET / PBT mass ratio in the entire polyester film based on the ratio of PET and PBT in each layer to the thickness of each layer. The value is shown after rounding the mass ratio to one decimal place. Furthermore, in the differential scanning calorimetry (DSC) measurements described later, polyester films PE9 and PE14 exhibit two melting peaks, while polyester films other than PE9 and PE14 exhibit one melting peak.

[0371] <Polyester film (PE1)>

[0372] The composition will be 70% by mass of PET (1), 20% by mass of PBT (1), and PET. MB(1) A mixture of raw materials in a ratio of 10% by mass was used as the raw material for the two surface layers, and a mixture of raw materials in a ratio of 80% by mass of PET (1) and 20% by mass of PBT (1) was used as the raw material for the intermediate layer. The raw materials for the two surface layers and the intermediate layer were fed to two extruders respectively. After melting at 280°C, they were co-extruded on a cooling roller set at 25°C with two three-layer structures (surface layer / intermediate layer / surface layer = 2.5 / 20 / 2.5 discharge rate) to cool and solidify, resulting in an unstretched sheet. Then, the obtained unstretched sheet was stretched to 3.5 times its length (longitudinal stretching) in the longitudinal dimension (MD) direction at 73°C using a roller stretcher. Then, after preheating at 75°C for 6 seconds in a tenter frame, it was stretched to 4.5 times its length (transverse stretching) in the width direction (TD) direction at 85°C. After stretching, a heat setting treatment of 8 seconds at 210°C is performed, followed by a cooling treatment of 140°C with 2% relaxation in the width direction to produce a biaxially stretched polyester film (PE1) with a thickness of 25μm (2.5μm for each surface layer and 20μm for the intermediate layer).

[0373] <Polyester film (PE2-5, PE8-13, PE15-16)>

[0374] By changing the type of raw materials, the thickness ratio and blending ratio of each layer, and the manufacturing conditions as described in Table 1, biaxially stretched polyester films (PE2-5, PE8-13, PE15-16) with a thickness of 25 μm were produced in the same manner as polyester film (PE1).

[0375] <Polyester film (PE6)>

[0376] The composition will be 68% by mass of PET (1) and 20% by mass of PBT (1). MB (1) A mixture of raw materials in a ratio of 12% by mass was used as the raw material for the two surface layers, and a mixture of raw materials in a ratio of 80% by mass of PET (1) and 20% by mass of PBT (1) was used as the raw material for the intermediate layer. The raw materials for the two surface layers and the intermediate layer were fed to two extruders respectively. After melting at 280°C, they were co-extruded on a cooling roller set at 25°C with two three-layer structures (surface layer / intermediate layer / surface layer = 2.1 / 20.8 / 2.1 discharge rate) to cool and solidify, resulting in an unstretched sheet. Then, the unstretched sheet was stretched along the longitudinal dimension (MD) at 73°C to 3.4 times (longitudinal stretching) using a roller stretching machine to produce a uniaxial stretched film. On one side of the uniaxial stretched film, a coating amount (after drying and stretching) of 0.05 g / m was applied. 2A coating solution having the following composition is applied to form a coating layer. Next, the film is preheated at 75°C for 7 seconds in a tenter frame, and then stretched 4.7 times its original length (transverse stretch) at 85°C along the width direction (TD). After stretching, a heat-setting treatment is performed at 209°C for 10 seconds, followed by a cooling treatment at 140°C with 2% relaxation along the width direction, to produce a biaxially stretched polyester film (PE6) with a thickness of 25 μm (2.1 μm for each surface layer and 20.8 μm for the intermediate layer) and a coating.

[0377] [Composition of the coating solution in the non-volatile components]

[0378] • 90% by mass of aqueous dispersion of polyester resin

[0379] Monomer composition: Polyester resin obtained by copolymerization of (acid component) terephthalic acid / isophthalic acid / sodium isophthalic acid-5-sulfonate / / (diol component) ethylene glycol / 1,4-butanediol / diethylene glycol = 56 / 40 / 4 / / 70 / 20 / 10 (mol%).

[0380] • Melamine compound: hexamethoxyhydroxymethyl melamine 9 by mass.

[0381] • Lubricant: 1 mass of silica particles with an average particle size of 0.07 μm.

[0382] <Polyester film (PE7)>

[0383] The composition will be 68% by mass of PET (1) and 20% by mass of PBT (1). MB (1) A mixture of raw materials in a ratio of 12% by mass was used as the raw material for the two surface layers, and a mixture of raw materials in a ratio of 80% by mass of PET (1) and 20% by mass of PBT (1) was used as the raw material for the intermediate layer. The raw materials for the two surface layers and the intermediate layer were fed to two extruders respectively. After melting at 280°C, they were co-extruded on a cooling roller set at 25°C with two three-layer structures (surface layer / intermediate layer / surface layer = 3.4 / 33.2 / 3.4 discharge rate) to cool and solidify, resulting in an unstretched sheet. Then, the obtained unstretched sheet was stretched to 3.5 times its length (longitudinal stretching) in the longitudinal dimension (MD) direction at 76°C using a roller stretcher. Then, after preheating at 75°C for 7 seconds in a tenter frame, it was stretched to 4.6 times its length (transverse stretching) in the width direction (TD) direction at 85°C. After stretching, a heat setting treatment was performed at 210°C for 10 seconds, followed by a cooling treatment at 140°C with 2% relaxation along the width direction to produce a biaxially stretched polyester film (PE7) with a thickness of 40μm (3.4μm for each surface layer and 33.2μm for the intermediate layer).

[0384] <Polyester film (PE14)>

[0385] The composition will be 65% by mass of PET (2), 20% by mass of PBT (2), and PET. MB (2) A mixture of raw materials in a ratio of 15% by mass was used as the raw material for the two surface layers, and a mixture of raw materials in a ratio of 45% by mass of PET (2) and 55% by mass of PBT (2) was used as the raw material for the intermediate layer. The raw materials for the two surface layers and the intermediate layer were fed to two extruders respectively. After melting at 280°C, they were co-extruded on a cooling roller set at 25°C with two three-layer structures (surface layer / intermediate layer / surface layer = 2.1 / 20.8 / 2.1 discharge ratio) to cool and solidify, resulting in an unstretched sheet. Then, the obtained unstretched sheet was stretched to 3.8 times its length (longitudinal stretching) in the longitudinal dimension (MD) direction at 70°C using a roller stretcher. Then, after preheating at 80°C for 6 seconds in a tenter frame, it was stretched to 5.2 times its length (transverse stretching) in the width direction (TD) direction at 80°C. After stretching, a heat setting treatment was performed at 180°C for 8 seconds, followed by a cooling treatment at 140°C with 2% relaxation along the width direction to produce a biaxially stretched polyester film (PE14) with a thickness of 25μm (2.1μm for each surface layer and 20.8μm for the intermediate layer).

[0386] <Polyester film (PE17)>

[0387] 90% by mass of PET (1) and PET MB (1) A mixture of raw materials in a ratio of 10% by mass was used as the raw material for the two surface layers, and a mixture of raw materials in a ratio of 80% by mass of PET (1) and 20% by mass of PBT (1) was used as the raw material for the intermediate layer. The raw materials for the two surface layers and the intermediate layer were fed to two extruders respectively. After melting at 280°C, they were co-extruded on a cooling roller set at 25°C with two three-layer structures (surface layer / intermediate layer / surface layer = 2.5 / 20 / 2.5 discharge rate) to cool and solidify, resulting in an unstretched sheet. Then, the unstretched sheet was stretched to 3.5 times (longitudinal stretching) along the longitudinal dimension (MD) at 76°C using a roller stretching machine to produce a uniaxial stretched film. On one side of the uniaxial stretched film, a coating amount (after drying and stretching) of 0.03 g / m was applied. 2 A coating solution having the following composition is applied to form a coating layer. Next, the film is preheated at 75°C for 7 seconds in a tenter frame, and then stretched 4.5 times its original length (transverse stretch) at 90°C along the width direction (TD). After stretching, a heat-setting treatment is performed at 210°C for 10 seconds, followed by a cooling treatment at 140°C with 2% relaxation along the width direction, to produce a biaxially stretched polyester film (PE17) with a thickness of 25 μm (2.5 μm for each surface layer and 20 μm for the intermediate layer) and a coating.

[0388] [Composition of the coating solution in the non-volatile components]

[0389] • 60 by mass of a compound containing long-chain alkyl groups, obtained by the following manufacturing method, which is formed by adding octadecyl isocyanate to polyvinyl alcohol with an average degree of polymerization of 500 and a degree of saponification of 88 mol%.

[0390] <Manufacturing Method>

[0391] 200 parts xylene and 600 parts octadecyl isocyanate were added to a four-necked flask and heated with stirring. Starting from the point when xylene began to reflux, 100 parts polyvinyl alcohol (PVA) with an average degree of polymerization of 500 and a degree of saponification of 88 mol% was added in small batches over approximately 2 hours at 10-minute intervals. After the addition of PVA was completed, the mixture was refluxed for another 2 hours to terminate the reaction. The reaction mixture was cooled to approximately 80°C and then added to methanol. The reaction product precipitated as a white precipitate. This precipitate was filtered and separated. 140 parts xylene were added and heated to completely dissolve the precipitate. Methanol was added again to precipitate the precipitate. This process was repeated several times. The precipitate was then washed with methanol, dried, and pulverized to obtain the final product.

[0392] • Melamine compound: Hexamethoxyhydroxymethyl melamine (partially etherified melamine with a hydroxymethyl to methoxy ratio of 1:2.2) 40 by mass.

[0393] [Table 1]

[0394]

[0395] Next, the raw materials for the polyamide layer, etc., used in the following examples and comparative examples are described below.

[0396] <<Polyamide layer>>

[0397] <Biaxially stretched polyamide 6 film (PA1)>

[0398] A 25 μm thick polyamide film was obtained by biaxial stretching.

[0399] <<Barrier Layer>>

[0400] <Aluminum alloy foil (ALM1)>

[0401] Aluminum alloy foils with a composition of JIS H4160:1994 A8079H-O and thicknesses of 40μm and 80μm.

[0402] <<Thermo-Melt Resin Layer>>

[0403] <Polypropylene resin>

[0404] Polypropylene (PP1, thicknesses of 22.5 μm and 40 μm) is used as a heat-melting resin layer.

[0405] <<Adhesive Layer>>

[0406] Two-component curing urethane adhesive

[0407] Two-component curing urethane adhesive (polyol compounds and aromatic isocyanate compounds).

[0408] <Polypropylene resin>

[0409] Maleic anhydride modified polypropylene (PPa1, thicknesses of 22.5 μm and 40 μm).

[0410] Using the polyester film (PE1 to PE17) for the substrate layer prepared above and various raw materials for other layers, laminates of the embodiments and comparative examples are prepared as described below.

[0411] [Example 1]

[0412] A barrier layer consisting of an aluminum alloy foil (ALM1) with an acid-resistant film formed on both sides is laminated onto a biaxially stretched polyamide film (PA1) serving as a polyamide layer using a dry lamination method. Specifically, a two-component curable urethane adhesive is applied as an adhesive layer to one side of the aluminum alloy foil (ALM1) with the acid-resistant film formed on both sides, forming an adhesive layer (3 μm thick after curing) on ​​the aluminum alloy foil (ALM1, 40 μm thick). Next, the adhesive layer on the aluminum alloy foil is laminated with the polyamide film (PA1), and then cured to produce a polyamide layer / adhesive layer / barrier layer laminate.

[0413] Next, using the same method as described above, a polyester film (PE1) is laminated on the biaxially stretched polyamide film (PA1) as a substrate layer by dry lamination to create a laminate of substrate layer / adhesive layer / polyamide layer / adhesive layer / barrier layer.

[0414] Next, maleic anhydride-modified polypropylene (PPa1, 22.5 μm thick) as an adhesive layer and polypropylene (PP1, 22.5 μm thick) as a hot-melt resin layer are co-extruded onto the aluminum alloy foil (ALM1), thereby stacking the hot-melt resin layer on the barrier layer to produce a laminate consisting of a substrate layer (25 μm) / adhesive layer (3 μm) / polyamide layer (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (22.5 μm) / hot-melt resin layer (22.5 μm) in sequence.

[0415] [Examples 2-6 and 9-11, Comparative Examples 1-6]

[0416] The polyester film (PE1) was replaced with the polyester films (PE2 to PE13 and PE15 to PE17) shown in Table 2. Otherwise, the laminates of Examples 2 to 6 and 9 to 11 and Comparative Examples 1 to 6 were prepared in the same manner as in Example 1.

[0417] It should be noted that Example 6 is a laminate formed by stacking an adhesive layer on a coating layer formed on a substrate layer, and then sequentially stacking a polyamide layer, an adhesive layer, a barrier layer, an adhesive layer, and a thermoplastic resin layer. Example 11 is a laminate formed by stacking an adhesive layer on the surface of a substrate layer on the side without a coating, and then sequentially stacking a polyamide layer, an adhesive layer, a barrier layer, an adhesive layer, and a thermoplastic resin layer.

[0418] [Examples 7, 13, 14]

[0419] A barrier layer consisting of an aluminum alloy foil (ALM1) with an acid-resistant film formed on both sides is laminated onto a biaxially stretched polyamide film (PA1) serving as a polyamide layer using a dry lamination method. Specifically, a two-component curable urethane adhesive is applied as an adhesive layer to one side of the aluminum alloy foil (ALM1, 80 μm thick) with an acid-resistant film formed on both sides, forming an adhesive layer (3 μm thick after curing) on ​​the aluminum alloy foil (ALM1). Next, the adhesive layer on the aluminum alloy foil is laminated to the polyamide film (PA1), and then cured to produce a polyamide layer / adhesive layer / barrier layer laminate.

[0420] Next, using the same method as described above, a polyester film (PE5, PE15, or PE16) is laminated on the biaxially stretched polyamide film (PA1) as the substrate layer by dry lamination to create a laminate of substrate layer / adhesive layer / polyamide layer / adhesive layer / barrier layer.

[0421] Next, maleic anhydride-modified polypropylene (PPa1, 40 μm thick) as an adhesive layer and polypropylene (PP1, 40 μm thick) as a hot-melt resin layer are co-extruded onto the aluminum alloy foil (ALM1), thereby stacking the hot-melt resin layer on the barrier layer to create a laminate consisting of a substrate layer (25 μm) / adhesive layer (3 μm) / polyamide layer (25 μm) / adhesive layer (3 μm) / barrier layer (80 μm) / adhesive layer (40 μm) / hot-melt resin layer (40 μm).

[0422] [Example 8]

[0423] A barrier layer consisting of an aluminum alloy foil (ALM1) with an acid-resistant film formed on both sides is laminated onto a biaxially stretched polyamide film (PA1) serving as a polyamide layer using a dry lamination method. Specifically, a two-component curable urethane adhesive is applied as an adhesive layer to one side of the aluminum alloy foil (ALM1) with the acid-resistant film formed on both sides, forming an adhesive layer (3 μm thick after curing) on ​​the aluminum alloy foil (ALM1, 80 μm thick). Next, the adhesive layer on the aluminum alloy foil is laminated with the polyamide film (PA1), and then cured to produce a polyamide layer / adhesive layer / barrier layer laminate.

[0424] Next, using the same method as described above, a polyester film (PE7) is laminated on the biaxially stretched polyamide film (PA1) as a substrate layer by dry lamination to create a laminate of substrate layer / adhesive layer / polyamide layer / adhesive layer / barrier layer.

[0425] Next, maleic anhydride-modified polypropylene (PPa1, 40 μm thick) as an adhesive layer and polypropylene (PP1, 40 μm thick) as a hot-melt resin layer are co-extruded onto the aluminum alloy foil (ALM1), thereby stacking the hot-melt resin layer on the barrier layer to create a laminate consisting of a substrate layer (40 μm) / adhesive layer (3 μm) / polyamide layer (25 μm) / adhesive layer (3 μm) / barrier layer (80 μm) / adhesive layer (40 μm) / hot-melt resin layer (40 μm) in sequence.

[0426] [Example 12]

[0427] A non-laminated biaxially stretched polyamide 6 film (PA1) was obtained, otherwise, in the same manner as in Example 1, a laminate consisting of a substrate layer (25 μm), an adhesive layer (3 μm), a barrier layer (40 μm), an adhesive layer (22.5 μm), and a heat-melting resin layer (22.5 μm) was obtained.

[0428] Specifically, a barrier layer consisting of an aluminum alloy foil (ALM1, 40 μm thick) with acid-resistant films formed on both sides is laminated onto a polyester film (PE1) as a substrate layer using a dry lamination method. Specifically, a two-component curable urethane adhesive is coated onto one side of the aluminum alloy foil (ALM1) with acid-resistant films formed on both sides, forming an adhesive layer (3 μm thick after curing) on ​​the aluminum alloy foil (ALM1). After laminating the adhesive layer with the polyester film (PE1), a curing treatment is performed, thereby producing a laminate of substrate layer / adhesive layer / barrier layer.

[0429] Next, maleic anhydride-modified polypropylene (PPa1, 22.5 μm thick) as an adhesive layer and polypropylene (PP1, 22.5 μm thick) as a hot-melt resin layer are co-extruded onto the aluminum alloy foil (ALM1), thereby stacking the hot-melt resin layer on the barrier layer to create a laminate consisting of a substrate layer (25 μm), an adhesive layer (3 μm), a barrier layer (40 μm), an adhesive layer (22.5 μm), and a hot-melt resin layer (22.5 μm) stacked sequentially.

[0430] [Comparative Example 7]

[0431] A non-laminated biaxially stretched polyamide 6 film (PA1) was obtained, except that, similar to Comparative Example 1, a laminate consisting of a substrate layer (25 μm), an adhesive layer (3 μm), a barrier layer (40 μm), an adhesive layer (22.5 μm), and a heat-melting resin layer (22.5 μm) was sequentially laminated.

[0432] Specifically, a barrier layer consisting of an aluminum alloy foil (ALM1, 40 μm thick) with acid-resistant films formed on both sides is laminated onto a polyester film (PE8) serving as the substrate layer using a dry lamination method. Specifically, a two-component curable urethane adhesive is coated onto one side of the aluminum alloy foil (ALM1) with acid-resistant films formed on both sides, forming an adhesive layer (3 μm thick after curing) on ​​the aluminum alloy foil (ALM1). After laminating the adhesive layer with the polyester film (PE8), a curing treatment is performed, thereby producing a laminate of substrate layer / adhesive layer / barrier layer.

[0433] Next, maleic anhydride-modified polypropylene (PPa1, 22.5 μm thick) as an adhesive layer and polypropylene (PP1, 22.5 μm thick) as a hot-melt resin layer are co-extruded onto the aluminum alloy foil (ALM1), thereby stacking the hot-melt resin layer on the barrier layer to create a laminate consisting of a substrate layer (25 μm), an adhesive layer (3 μm), a barrier layer (40 μm), an adhesive layer (22.5 μm), and a hot-melt resin layer (22.5 μm) stacked sequentially.

[0434] [Comparative Example 8]

[0435] A biaxially stretched polyamide 6 film (PA1) was not laminated. Otherwise, a laminate containing a substrate layer (25 μm), an adhesive layer (3 μm), a barrier layer (40 μm), an adhesive layer (22.5 μm), and a heat-melting resin layer (22.5 μm) was obtained in the same manner as in Comparative Example 6.

[0436] Specifically, a barrier layer consisting of an aluminum alloy foil (ALM1) with acid-resistant films formed on both sides is laminated onto a polyester film (PE13) serving as a substrate layer using a dry lamination method. Specifically, a two-component curable urethane adhesive is applied as an adhesive layer to one side of the aluminum alloy foil (ALM1) with acid-resistant films formed on both sides, forming an adhesive layer (3 μm thick after curing) on ​​the aluminum alloy foil (ALM1, 40 μm thick). After laminating the adhesive layer with the polyester film (PE13), a curing treatment is performed, thereby producing a laminate of substrate layer / adhesive layer / barrier layer.

[0437] Next, maleic anhydride-modified polypropylene (PPa1, 22.5 μm thick) as an adhesive layer and polypropylene (PP1, 22.5 μm thick) as a hot-melt resin layer are co-extruded onto the aluminum alloy foil (ALM1), thereby stacking the hot-melt resin layer on the barrier layer to create a laminate consisting of a substrate layer (25 μm), an adhesive layer (3 μm), a barrier layer (40 μm), an adhesive layer (22.5 μm), and a hot-melt resin layer (22.5 μm) stacked sequentially.

[0438] [Comparative Example 9]

[0439] A barrier layer consisting of an aluminum alloy foil (ALM1) with an acid-resistant film formed on both sides is laminated onto a polyester film (PE14) serving as a substrate layer using a dry lamination method. Specifically, a two-component curable urethane adhesive is coated onto one side of the aluminum alloy foil (ALM1, 40 μm thick) with an acid-resistant film formed on both sides, forming an adhesive layer (3 μm thick after curing) on ​​the aluminum alloy foil (ALM1). After laminating the adhesive layer with the polyester film (PE14), a curing treatment is performed, thereby producing a laminate of substrate layer / adhesive layer / barrier layer.

[0440] Next, maleic anhydride-modified polypropylene (PPa1, 22.5 μm thick) as an adhesive layer and polypropylene (PP1, 22.5 μm thick) as a hot-melt resin layer are co-extruded onto the aluminum alloy foil (ALM1), thereby stacking the hot-melt resin layer on the barrier layer to create a laminate consisting of a substrate layer (25 μm), an adhesive layer (3 μm), a barrier layer (40 μm), an adhesive layer (22.5 μm), and a hot-melt resin layer (22.5 μm) stacked sequentially.

[0441] <<Measurement Methods / Evaluation Methods>>

[0442] The results obtained by measuring the various properties of the polyester film obtained above using the following measurement methods are shown in Tables 2 and 3, and the results obtained by evaluating the formability and heat resistance of the laminate obtained above using the following methods are also shown in Tables 2 and 3.

[0443] It should be noted that the tensile yield stress (MPa), tensile elongation at break (%), and tensile stress at break (MPa) in Tables 2 and 3 are values ​​obtained by rounding the measured values ​​to one decimal place. The slope of the stress-strain curve is a value obtained by rounding the measured values ​​to three decimal places. The difference between the slopes of the stress-strain curves (MPa / %) is a value obtained by rounding the ratio of the measured values ​​to three decimal places.

[0444] [Tensile yield stress, tensile elongation at break, and tensile stress of polyester film]

[0445] Tensile properties of a sample piece measuring 15 mm in width direction (TD) and 150 mm in length direction (MD) were measured from a polyester film. Similarly, tensile properties of a sample piece measuring 15 mm in width direction (TD) and 150 mm in length direction (MD) were measured from a polyester film. Following JIS K 7161-1 (2014), a Shimadzu Autograph AGX-V tensile testing machine was used. The sample piece for measuring tensile properties in the length direction (MD) was used to measure the tensile yield stress, elongation at break (nominal strain at tensile failure), and tensile stress in the length direction (MD). The sample piece for measuring tensile properties in the width direction (TD) was also used to measure the tensile yield stress, elongation at break (nominal strain at tensile failure), and tensile stress in the width direction (TD). The test was conducted under the following conditions: at 23°C and 50%RH, punctuation marks were marked at 50mm intervals in the center of each test piece, the distance between the chucks of the test pieces was 50mm, and the tensile speed was 200mm / min.

[0446] [The slope of the curve between the yield point and the fracture point in the stress-strain curve of the polyester film, and the difference (absolute value) between MD and TD of this slope]

[0447] Tensile properties in the longitudinal direction (MD) were measured using specimens of 15 mm in width (TD) and 150 mm in width (MD) from polyester film. Following JIS K 7161-1 (2014), Shimadzu Corporation's "Autograph AGX-V" was used. For the longitudinal direction (MD) tensile properties test, the slope of the stress-strain curve between the yield point and the fracture point was measured using specimens for the longitudinal direction (MD). Similarly, for the width direction (TD) tensile properties test, the slope of the stress-strain curve between the yield point and the fracture point was measured using specimens for the width direction (TD). The measurements were performed under the following conditions: 23°C, 50%RH atmosphere, with 50 mm intervals marked at the center of each specimen, a chuck spacing of 50 mm between specimens, and a tensile speed of 200 mm / min.

[0448] The slopes of each stress-strain curve were calculated using the least squares method of the regression line. In the calculation, the number of measurement points was set to one every 0.1 seconds, using more than 100 data points, and the calculations were performed using the LINEST function in Microsoft Excel.

[0449] [Melting point (Tm) of polyester film]

[0450] According to JIS K7121 (2012), for polyester films, a Diamond DSC (PerkinElmer Japan) was used as the differential scanning calorimeter. The temperature was increased from -70°C to 280°C at a heating rate of 10°C / min to reach the melting temperature in one step, then held for 10 minutes. Next, the temperature was decreased to -70°C at a cooling rate of 600°C / min, and then increased again from -70°C to 280°C at a heating rate of 10°C / min. The melting point of the first heating scan was determined by the value of the peak tip (melting peak temperature) observed during the first heating process, and the melting point of the second heating scan was determined by the peak tip (melting peak temperature) observed during the second heating process. It should be noted that when more than two melting peaks are observed, the temperature of the peak tip of the largest peak is taken as the melting point.

[0451] [Glass transition temperature (Tg) of polyester film]

[0452] According to JIS K7121 (2012), for polyester films, a Diamond DSC (manufactured by PerkinElmer Japan) was used as a differential scanning calorimeter. The temperature was temporarily raised to the melting temperature at a heating rate of 10°C / min in the range of -70 to 280°C, and then held for 10 minutes. Then, the temperature was cooled to -70°C at a cooling rate of 600°C / min, and then raised to -70 to 280°C again at a heating rate of 10°C / min. The glass transition temperature at the midpoint of this second heating process was measured.

[0453] [Formability of Laminated Structures]

[0454] Test pieces measuring 90 mm in the longitudinal direction (MD) and 150 mm in the width direction (TD) were collected from the laminate. The longitudinal direction (MD) of the laminate corresponds to the rolling direction (RD) of the aluminum alloy foil, and the width direction (TD) of the laminate corresponds to the TD of the aluminum alloy foil. At 25°C, a forming die (female die, with a maximum height roughness (nominal value of Rz) of 3.2 μm as specified in Table 2 of Appendix 1 (Reference) of JIS B0659-1:2002 for comparative surface roughness standard sheets) and a corresponding forming die (male die, with a diameter of 31.6 mm (MD) × 54.5 mm (TD) and a surface roughness standard sheet of 3.2 μm as specified in Table 2 of Appendix 1 (Reference) of JIS B0659-1:2002) were used. Appendix 1 (Reference) of 0659-1:2002 specifies a maximum height roughness (nominal value of Rz) of 1.6 μm as specified in Table 2 of the comparative surface roughness standard sheet. With corners R2.0 mm and edges R1.0 mm, under a pressing pressure (surface pressure) of 0.25 MPa, 23°C, and 50% RH, the forming depth of the test piece was changed in 0.5 mm increments, starting from a forming depth of 0.5 mm. Ten test pieces were cold-formed (introducing a forming section) to form a rectangular receiving part (the receiving part of a lithium-ion battery) when viewed from above. At this time, the test piece was placed on the female mold with the hot-melt resin layer side facing the male mold side for forming. Furthermore, the gap between the male and female molds was set to 0.3 mm. For the cold-formed samples, a flashlight was used to illuminate them in a dark room, and the presence of pinholes or cracks in the aluminum alloy foil was confirmed through light transmission. The deepest molding depth in which no pinholes or cracks were produced on the aluminum alloy foil among the 10 samples is set as A mm. The number of samples in which pinholes or cracks were produced at the shallowest molding depth on the aluminum alloy foil is set as B. The value calculated by the following formula is rounded to two decimal places and is taken as the limit molding depth of the outer casing material for the energy storage device.

[0455] Limiting forming depth = Amm + (0.5mm / 10 pieces) × (10 pieces - B pieces)

[0456] (Evaluation Criterion 1)

[0457] A laminate consisting of identical layers of PE8 with the same thickness is designated as a "reference example," and the limit molding depth is compared and evaluated.

[0458] S……The maximum forming depth is the reference example +1.5mm or more.

[0459] A……The limit forming depth is more than 1 mm above the reference example and less than 1.5 mm below the reference example.

[0460] B……The limit forming depth is greater than or equal to the reference example +0.5mm and less than the reference example +1mm.

[0461] C……The limit forming depth is greater than or equal to +0 mm of the reference example and less than +0.5 mm of the reference example.

[0462] D……The limit forming depth is less than the reference example.

[0463] It should be noted that, in the case of Example 1 and Comparative Example 1, the "reference example" refers to the laminate prepared as follows.

[0464] (Preparation of the reference example for Example 1)

[0465] The polyester film (PE1) used as the substrate layer was changed to a polyester film (PE8).

[0466] Specifically, a barrier layer consisting of an aluminum alloy foil (ALM1) with an acid-resistant film formed on both sides is laminated onto a biaxially stretched polyamide film (PA1) serving as a polyamide layer using a dry lamination method. Specifically, a two-component curable urethane adhesive is applied as an adhesive layer to one side of the aluminum alloy foil (ALM1, 40 μm thick) with the acid-resistant film formed on both sides, forming an adhesive layer (3 μm thick after curing) on ​​the aluminum alloy foil (ALM1). Next, the adhesive layer on the aluminum alloy foil is laminated with the polyamide film (PA1), and then cured to produce a polyamide layer / adhesive layer / barrier layer laminate.

[0467] Next, using the same method as described above, a polyester film (PE8) is laminated on the biaxially stretched polyamide film (PA1) as a substrate layer by dry lamination to create a laminate of substrate layer / adhesive layer / polyamide layer / adhesive layer / barrier layer.

[0468] Next, maleic anhydride-modified polypropylene (PPa1, 22.5 μm thick) as an adhesive layer and polypropylene (PP1, 22.5 μm thick) as a hot-melt resin layer are co-extruded onto the aluminum alloy foil (ALM1), thereby stacking the hot-melt resin layer on the barrier layer to produce a laminate consisting of a substrate layer (25 μm) / adhesive layer (3 μm) / polyamide layer (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (22.5 μm) / hot-melt resin layer (22.5 μm) in sequence.

[0469] (The creation of reference examples for Comparative Example 1 and Comparative Example 7)

[0470] The reference example for the moldability evaluation of Examples 1-11, Examples 13, Examples 14, and Comparative Examples 1-6 recorded in Table 2 is Comparative Example 1, and the reference example for the moldability evaluation of Examples 12 and Comparative Examples 7-9 recorded in Table 3 is Comparative Example 7.

[0471] Comparative Example 1 originally used "PE8", therefore, Comparative Example 1 and its reference example are the same laminate. That is, the moldability evaluation of Comparative Example 1 represents the result compared with the same laminate. Therefore, the evaluation is C (the limiting molding depth is more than or equal to the reference example +0 mm and less than the reference example +0.5 mm).

[0472] It should be noted that Comparative Example 7 was also rated C for the same reason (the limit forming depth is greater than or equal to +0 mm of the reference example and less than +0.5 mm of the reference example).

[0473] (Evaluation Criterion 2)

[0474] To confirm the effect of the presence or absence of the polyamide layer, Example 12 without the polyamide layer was used as a "reference example," and the limit molding depth of Example 1 with the polyamide layer was evaluated using the same criteria as the evaluation benchmark 1.

[0475] Compared to Example 12, Example 1 has a maximum molding depth that is greater than or equal to Reference Example + 1 mm but less than Reference Example + 1.5 mm, and is rated A.

[0476] [Heat resistance of laminates]

[0477] Test pieces measuring 120 mm in length (MD) and 60 mm in width (TD) were collected from the laminate. The test pieces were folded with the substrate layer facing outwards and half the length of the MD (60 mm). The long dimension (MD) and width (TD) orientations of the heat-sealing resin layers were aligned. Heat sealing was performed using a TESTTER SANGYO TP-701-B heat-sealing tester with a Teflon (registered trademark) coating on the sealing rod surface, at the specified heat-sealing temperature of 200–230°C as shown in Tables 2 and 3, under the following conditions: surface pressure 1.0 MPa, sealing time 3 seconds, sealing width 7 mm, ambient temperature 23°C, and ambient humidity 50% RH. The surface appearance of the laminate after heat sealing and the presence or absence of fusion between the laminate and the heat-sealing rod were visually observed and evaluated according to the following criteria.

[0478] It should be noted that in Example 11, the test piece was folded with the coating on the outside and heat-sealed in the same order as above. The presence or absence of fusion between the laminate and the coating side surface (equivalent to the substrate side surface of the laminate) and the heat-sealing rod was visually observed and evaluated according to the following criteria.

[0479] In addition, "heat sealing temperature" refers to the set temperature of the heat source of the heat sealing tester.

[0480] (Evaluation Criteria)

[0481] S... The appearance of the substrate side surface of the laminate remains unchanged, and there is no fusion between the substrate side surface and the heat sealing bar.

[0482] A... There is slight whitening on the side surface of the laminate substrate, or slight fusion of the side surface of the laminate substrate to the heat-sealing bar.

[0483] B... The side surface of the laminate substrate is whitened, or there is a weld from the side surface of the laminate substrate to the heat sealing bar.

[0484] C... There are two aspects: whitening of the substrate side surface of the laminate and welding of the substrate side surface of the laminate to the heat-sealing rod.

[0485] [Table 2]

[0486]

[0487] [Table 3]

[0488]

[0489] As described above, in the past, when using a laminate containing a polyester film to form a bag body through heat fusion in the outer casing material of energy storage devices used for sealing electrodes, electrolytes, etc., the following problems would occur: the polyester film of the laminate has low heat resistance, so whitening will occur on the surface after heat fusion, thereby reducing the surface appearance of the resulting bag body; or the laminate is fused to the heat sealing bar used in heat fusion. Furthermore, if the content of polybutylene terephthalate is reduced in order to improve heat resistance, even if the polyamide has excellent deep drawing formability, problems such as the periphery of the recess will break if a deep recess is to be formed will occur. However, as shown in Tables 2 and 3, it can be seen that if the laminate of Examples 1 to 14 of the present invention is used, the change in surface appearance and the fusion of the laminate to the heat sealing bar can be sufficiently suppressed. In addition, local stress concentration during molding is suppressed and stress uniformity is promoted. As a result, the deep drawing formability is also excellent, so both formability and heat resistance can be taken into account. It should be noted that the heat resistance of the laminates of Examples 1 to 8 at a heat sealing temperature of 230°C is rated as "C". However, heat sealing is usually carried out in the temperature range up to about 220°C. Therefore, it can be said that the laminates of Examples 1 to 8 also have heat resistance that can withstand actual use.

[0490] Specifically, for example, as shown in Table 2, Example 1, which uses polyester film (PE1) as the substrate layer, exhibits relatively improved formability compared to the reference example which uses polyester film (PE8) as the substrate layer. Furthermore, Example 1, which uses polyester film (PE1) as the substrate layer, also demonstrates excellent heat resistance (it should be noted that heat resistance is not a relative evaluation compared to the reference example, but an absolute evaluation).

[0491] On the other hand, as shown in Tables 2 and 3, it can be seen that in the laminates of Comparative Examples 1 to 9, the mass ratio of polyethylene terephthalate to polybutylene terephthalate in the substrate layer was not controlled within the range of 65 / 35 to 90 / 10, and the tensile elongation at break in the width direction was not controlled within the range of 90% or more and 155% or less, thus failing to balance formability and heat resistance. Moreover, it can be seen, for example, that when a polyester film (PE8) containing only polyethylene terephthalate and polybutylene terephthalate is used, as in Comparative Examples 1 and 7, and which has a high tensile yield stress in the MD, although the heat resistance is excellent, it is impossible to balance formability and heat resistance.

[0492] Furthermore, it is known that even when both polyethylene terephthalate and polybutylene terephthalate are present, in the case of using a polyester film (PE9) with a high proportion of polybutylene terephthalate and low tensile yield stress of MD and TD, as in Comparative Example 2, there is no improvement in formability, the heat resistance becomes insufficient, and it is impossible to balance formability and heat resistance.

[0493] Furthermore, it is known that when a polyester film (PE10) containing a high proportion of polybutylene terephthalate (PET) with low elongation at break and high tensile stress of TD is used, as in Comparative Example 3, there is no improvement in formability, the heat resistance becomes insufficient, and it is impossible to balance formability and heat resistance.

[0494] Similarly, it can be seen that even when both polyethylene terephthalate and polybutylene terephthalate are present, in the case of using a polyester film (PE12) with a high proportion of polybutylene terephthalate, low tensile yield stress of MD and low tensile elongation at break of TD, as in Comparative Example 5, there is no improvement in formability, and it is impossible to balance formability and heat resistance.

[0495] Furthermore, it is known that when a polyester film (PE13) containing a high proportion of polybutylene terephthalate (PPT) with low tensile yield stress of MD and low tensile elongation at break of TD is used, as in Comparative Examples 6 and 8, the heat resistance becomes insufficient, and it is impossible to balance moldability and heat resistance.

[0496] Similarly, it can be seen that even when both polyethylene terephthalate and polybutylene terephthalate are present, in the case of using a polyester film (PE14) with a high proportion of polybutylene terephthalate, low tensile yield stress of MD, low tensile elongation at break of TD, and low tensile stress at break of MD, as in Comparative Example 9, there is no improvement in formability, the heat resistance becomes insufficient, and it is impossible to balance formability and heat resistance.

[0497] Furthermore, it is known, for example, that even when polyethylene terephthalate and polybutylene terephthalate are contained within the mass ratio range (65 / 35 to 90 / 10) specified in this invention, the heat resistance is not sufficient when using a polyester film (PE11) with low tensile breaking stress of MD, as in Comparative Example 4, and it is impossible to balance moldability and heat resistance.

[0498] (Regarding the presence or absence of a polyamide layer)

[0499] As described above, to confirm the effect of the presence or absence of the polyamide layer, Example 12 without the polyamide layer was used as a reference example. The limiting molding depth of Example 1 with the polyamide layer was evaluated using the same criteria as Evaluation Criterion 1 described above. The result was that, compared to Example 12, the limiting molding depth of Example 1 was at least 1 mm longer than that of Example 12 and less than 1.5 mm longer than that of Example 1, and the evaluation was A. Based on this result, it can be seen that by fabricating a laminate with a polyamide layer, the moldability can be improved.

[0500] Furthermore, it has been found that in the examples using polyester films containing polyethylene terephthalate and polybutylene terephthalate in the range of mass ratios (65 / 35 to 90 / 10) specified in this invention, as shown in Examples 9-11, 13, and 14, the heat resistance is excellent when the content of polyethylene terephthalate in the surface layer is relatively high.

[0501] In summary, the outer casing material for energy storage devices, which includes a laminate comprising a polyester film that fully satisfies the various requirements of the present invention as a substrate layer and sequentially comprises the substrate layer, a polyamide layer, a barrier layer, and a heat-melting resin layer, can achieve a high balance between heat resistance and formability.

[0502] The above embodiments illustrate specific aspects of the present invention, but these embodiments are merely examples and not intended to be limiting. It is intended that various modifications, obvious to those skilled in the art, fall within the scope of the present invention.

[0503] Industrial availability

[0504] According to the present invention, an outer casing material for energy storage devices with excellent formability and heat resistance can be provided. It is particularly suitable as a battery bag (packaging) for relatively high-capacity lithium-ion batteries.

[0505] Explanation of reference numerals in the attached figures

[0506] 1: Substrate layer;

[0507] 2: First adhesive layer;

[0508] 3: Polyamide layer;

[0509] 4: Second adhesive layer;

[0510] 5: Barrier layer;

[0511] 6: Thermo-meltable resin layer.

Claims

1. An outer casing material for an energy storage device, said outer casing material being composed of a laminate comprising at least a substrate layer, a barrier layer, and a heat-melting resin layer in sequence. The substrate layer is a polyester film containing polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 65 / 35 to 90 / 10. The polyester film has a tensile elongation at break of 90% or more and 155% or less in the width direction.

2. The external casing material for the energy storage device according to claim 1, wherein, A polyamide layer is provided between the substrate layer and the barrier layer.

3. The casing material for a storage device according to claim 1 or 2, wherein, The tensile yield stress in the long dimension of the polyester film is above 80 MPa and below 105 MPa.

4. The casing material for an energy storage device according to any one of claims 1 to 3, wherein, The tensile yield stress in the width direction of the polyester film is above 65 MPa and below 110 MPa.

5. The casing material for an energy storage device according to any one of claims 1 to 4, wherein, The polyester film has a tensile elongation at break of 110% or more and 190% or less in the long dimension.

6. The casing material for an energy storage device according to any one of claims 1 to 5, wherein, The tensile breaking stress in the longitudinal direction of the polyester film is 160 MPa or more and 260 MPa or less, and the tensile breaking stress in the transverse direction of the polyester film is 190 MPa or more and 290 MPa or less.

7. The casing material for an energy storage device according to any one of claims 1 to 6, wherein, The elongation at break in the width direction of the polyester film is less than or equal to the elongation at break in the length direction of the polyester film.

8. The casing material for an energy storage device according to any one of claims 1 to 7, wherein, The tensile breaking stress in the width direction of the polyester film is greater than or equal to the tensile breaking stress in the length direction of the polyester film.

9. The casing material for a storage device according to any one of claims 1 to 8, wherein, The slope of the curve corresponding to the yield point to the fracture point in the stress-strain curve of the polyester film is greater than or equal to 0.60 MPa / % and less than or equal to 1.20 MPa / % in the long dimension direction, and greater than or equal to 1.00 MPa / % and less than or equal to 1.80 MPa / % in the width direction.

10. The casing material for a storage device according to claim 9, wherein, The absolute value of the difference between the slope of the curve in the long dimension direction and the slope of the curve in the width direction is less than 1.10 MPa / %.

11. The casing material for an energy storage device according to any one of claims 1 to 10, wherein, The melting point of the polyester film during the first temperature scan is above 230°C.

12. The casing material for an energy storage device according to any one of claims 1 to 11, wherein, An adhesive layer is provided between the substrate layer and the barrier layer.

13. The casing material for an energy storage device according to any one of claims 1 to 12, wherein, A polyamide layer composed of a stretch film is provided between the substrate layer and the barrier layer.

14. The casing material for an energy storage device according to any one of claims 1 to 13, wherein, The barrier layer contains aluminum.

15. The casing material for an energy storage device according to any one of claims 1 to 14, wherein, The polyester film is composed of two or more laminates.

16. The casing material for an energy storage device according to any one of claims 1 to 15, wherein, The polyester film comprises a surface layer, an intermediate layer, and another surface layer in sequence.

17. The casing material for an energy storage device according to any one of claims 1 to 16, wherein, The polyester film comprises a surface layer, an intermediate layer, and another surface layer in sequence, wherein the thickness of the intermediate layer is greater than the thickness of the surface layer.

18. The casing material for an energy storage device according to any one of claims 1 to 17, wherein, The polyester film comprises a surface layer, an intermediate layer, and another surface layer in sequence, and the thickness ratio of each layer is 1-1.6:8-12:1-1.6, calculated as the thickness of the surface layer: the thickness of the intermediate layer: the thickness of the surface layer.

19. The casing material for an energy storage device according to any one of claims 1 to 18, wherein, The polyester film is composed of two or more laminates, and the material composition forming one surface layer is different from the material composition forming at least one of the other layers.

20. The casing material for an energy storage device according to any one of claims 1 to 19, wherein, The polyester film comprises a surface layer, an intermediate layer, and another surface layer in sequence, wherein the material composition of the surface layer is different from that of the intermediate layer.

21. The casing material for an energy storage device according to any one of claims 1 to 20, wherein, The polyester film is composed of two or more laminates, wherein the content of polyethylene terephthalate in one surface layer is greater than the content of polyethylene terephthalate in at least one of the other layers.

22. The casing material for an energy storage device according to any one of claims 1 to 21, wherein, The polyester film is composed of two or more laminates, wherein the content of polyethylene terephthalate in one surface layer is greater than the content of polyethylene terephthalate in at least one of the other layers, and the surface layer is located on the outermost side of the laminate.

23. The casing material for an energy storage device according to any one of claims 1 to 22, wherein, The polyester film comprises a top layer, an intermediate layer, and another top layer in sequence, wherein the content of polyethylene terephthalate in the top layer is greater than the content of polyethylene terephthalate in the intermediate layer.

24. The casing material for an energy storage device according to any one of claims 1 to 23, wherein, The polyester film is composed of two or more laminates, one of which contains polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 100 / 0 to 90 / 10.

25. The casing material for an energy storage device according to any one of claims 1 to 24, wherein, The polyester film is composed of two or more laminates, one of which contains polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 100 / 0 to 90 / 10, and the surface layer is present on the outermost side of the laminate.

26. The casing material for an energy storage device according to any one of claims 1 to 25, wherein, The polyester film comprises a surface layer, an intermediate layer, and another surface layer in sequence, wherein the surface layer contains polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 100 / 0 to 90 / 10.

27. The casing material for an energy storage device according to any one of claims 1 to 26, wherein, The melting peak of the polyester film during heating is one, which is obtained from at least one of the first and second heating scans based on differential scanning calorimetry.

28. The casing material for an energy storage device according to any one of claims 1 to 27, wherein, At least one surface of the polyester film has a coating.

29. The casing material for an energy storage device according to any one of claims 1 to 28, wherein, The polyester film has a coating on at least one surface, the coating containing a long-chain alkyl compound and a melamine compound in a mass ratio of 95 / 5 to 5 / 95.

30. The casing material for an energy storage device according to any one of claims 1 to 29, wherein, The intrinsic viscosity of the polyethylene terephthalate contained in the polyester film is above 0.50 dL / g.

31. The casing material for an energy storage device according to any one of claims 1 to 30, wherein, The intrinsic viscosity of the polybutylene terephthalate contained in the polyester film is above 0.70 dL / g.

32. The casing material for an energy storage device according to any one of claims 1 to 31, wherein, The polyester film is a biaxially stretched film, and the product of the stretch ratio in the width direction and the stretch ratio in the length direction of the polyester film exceeds 15.

5.

33. The casing material for an energy storage device according to any one of claims 1 to 32, wherein, The polyester film is a biaxially stretched film, and the difference between the stretch ratio in the width direction and the stretch ratio in the length direction of the polyester film is more than 0.3 times.

34. The casing material for an energy storage device according to any one of claims 1 to 33, wherein, The polyester film is a biaxially stretched film, and the ratio of the stretch ratio in the width direction to the stretch ratio in the length direction, i.e., the stretch ratio in the width direction / the stretch ratio in the length direction, is 1.2 or more and 1.7 or less.

35. An energy storage device comprising an energy storage device element having at least a positive electrode, a negative electrode, and an electrolyte, housed in a package formed of an outer packaging material for an energy storage device as described in any one of claims 1 to 34.

36. A method for manufacturing an outer casing material for an energy storage device, the method comprising at least one step of sequentially stacking a substrate layer, a barrier layer, and a heat-melting resin layer to obtain a laminate. A polyester film is used in the substrate layer. The polyester film contains polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 65 / 35 to 90 / 10. The polyester film has a tensile elongation at break of 90% or more and 155% or less in the width direction.

37. The method for manufacturing the outer casing material for a storage device according to claim 36, wherein, The process of obtaining the laminate is a process of obtaining a laminate that sequentially comprises at least a substrate layer, a polyamide layer, a barrier layer, and a heat-melting resin layer. The polyester film has a tensile yield stress of 80 MPa or more and 105 MPa or less in the longitudinal direction, a tensile yield stress of 65 MPa or more and 110 MPa or less in the transverse direction, and a tensile elongation at break of 110% or more and 190% or less in the longitudinal direction.

Citation Information

Patent Citations

  • Polybutylene terephthalate film

    JP2012077292A

  • Polyester film for cold forming and method for producing same

    WO2014017457A1